Contrasting organic amendments drive divergent aggregate-bound mineral-associated carbon and nitrogen stabilization pathways in rainfed spring maize soils - Yan Gao; Binbin Cao; Hui Xia; Tian Chen; Yunuo Li; Jiaqi Hao; Jianglan Shi; Xiaohong Tian (Agriculture, Ecosystems & Environment, 2027)

Emergence of an optrA-positive Enterococcus faecalis ST699 lineage in animal-derived foods in Beijing, China - Chuncai Liang; Yizhu Chen; Xuan Wu; Rui Chang; Wenkai Cao; Ling Wei; Hui Li; Bing Shao (International Journal of Food Microbiology, 2026)

Potato residue chips as corn replacement in Angus bulls: Effects on carcass characteristics, meat quality, and serum metabolites - Chang-Xiao Shi; Hui-Li Wang; Ying-Qi Li; Muhammad Aziz-ur-Rahman; Si-Yu Zhang; Jia-Jie Deng; Wen-Xi Zhao; Xing-Yue Yi; Yi-Min Zhang; Yang He; Bing-hai Cao; Hua-Wei Su (Food and Humanity, 2026)

Sedimentary characteristics of the Ganges Submarine Delta and its response to chemical weathering during the Mid-Holocene - Hongmin Wang; Lina Ai; Ashraf Ali Seddique; Bingjie Sun; Hui Zhang; Xiaoyan Li; Peng Cao; Kaikai Wu; Kunshan Wang; Shengfa Liu (Quaternary International, 2026)

Tailoring microstructure of coal-based hard carbon and electrochemical performance for sodium-ion battery anodes: Insights from the intrinsic properties of diverse coal precursors - Weibo Meng; Hui Guo; Baolin Xing; Qiaomiao Xu; Man Wang; Long Li; Huihui Zeng; Xiaoxiao Qu; Chuanxiang Zhang; Peng Li; Yijun Cao (Fuel, 2026)

Topology-directed construction of 2D In-MOF-derived defect-rich carbon nanosheets for supported FePc catalysis in oxygen reduction - Yuchang Shen; Xinyuan Xu; Nan Li; Hui Liu; Yuanjie Cao; Weiyu Luo; Li Zhong; Qipeng Li; Linjie Zhang; Jinjie Qian (Chemical Engineering Journal, 2026)

The greenhouse gas emissions characteristics and reduction pathways for the shipping industry - Weijie Xiong; Kai Wang; Yanpo Chi; Hui Xing; Hongzhi Liang; Zhongwei Li; Xiang Zhang; Jianlin Cao (Marine Pollution Bulletin, 2026)

Immunomodulatory effects of octopamine in Procambarus clarkii - Qing Li; Yinan Jiang; Yangyang Cao; Zhiqiang Zhang; Liuyang Zhang; Yangyan Kang; Yingying Zhang; Hui Yang (Aquaculture, 2026)

Intranasal BCG cell wall polysaccharide-based subunit vaccine confers protection against Mycobacterium bovis challenge in mice - Na Li; Mengting Zhou; Yinjuan Song; Li Tang; Hui Ma; Jian Xu; Jian Cao; Na Li; Yuefeng Chu (Veterinary Microbiology, 2026)

Differences in watershed hydrochemical evolution driven by anthropogenic disturbances and geological heterogeneity: from source apportionment to hydrological process response - Qi Long; Hui Qian; Yicheng Duan; Kang Li; Yanyan Gao; Yixin Liu; Siqi Li; Xiaoxin Shi; Zhiming Cao; Qiaoyang Yang (Journal of Hydrology, 2026)

Chemical-free closed-loop conversion of nitrate into struvite fertilizer via exsolved high-entropy perovskite electrocatalyst - Li-Hui Yang; Yi-Heng Liu; Si-Hao Lv; Man-Ting Liao; Hui Lin; Wei Li; Cao Yang; An-Qi Wang; Hao-Yi Cheng (Journal of Environmental Chemical Engineering, 2026)

Bidirectional regulation of heterocyclic amines by flavonoids: insights from flavonoid amination using dihydromyricetin and baicalein - Jingjing Zhang; Hui Cao; Bing Li; Fuying Wang; Qin Duan; Yaru Li; Jinjin Pei; Hui Wang; Juan Carlos Mejuto; Jesús Simal-Gándara; Haolin Zhang (Food Chemistry, 2026)

An objective detection method for tinnitus using memristors - Hui Ma; Xiaoyan Ma; Yingying Xuan; Zelin Cao; Lin Li; Kaikai Gao; Mengna Wang; Ruifeng Qiao; Qin Hu; Wentao Yan; Kun Wang; Haoyuan Wang; et al. (Chemical Engineering Journal, 2026)

Milk vetch activates low-grade phosphate rock for phosphorus supply and cadmium mitigation in paddy fields - Jiancheng Xie; Danna Chang; Xinyan Li; Ting Liang; Xiaofen Chen; Jia Liu; Changxu Xu; Rongyan Bu; Hui Wang; Ji Wu; Songjuan Gao; Weidong Cao (Journal of Hazardous Materials, 2026)

Synergistic effects of phosphatidylcholine and cholesterol on lipid droplet interfacial structure and in vitro digestibility of simulated breast milk fat emulsion - Hongbo Li; Naibin Zhang; Suling Tian; Boan Yu; Hui Chen; Yongqiang Cao; Hongjuan Li; Jinghua Yu (Food Research International, 2026)

Matrix-dependent inhibitory pattern of flavonoids against polycyclic aromatic hydrocarbons: reversed structure-activity relationship from glucose simulation model to roasted meat system - Haolin Zhang; Qiuyi Lin; Le Long; Huaxing Xiong; Yaru Li; Hui Cao (Food Chemistry, 2026)

Linking hydrological exchange and DOM transformation in a semi-arid river: Insights from isotopic and fluorescent fingerprinting - Yanyan Gao; Xinjie Xu; Panpan Tian; Hui Qian; Xiaoxin Shi; Zhiming Cao; Hao Huang; Jinkun Zhang; Zeyu Shi; Yixin Liu; Siqi Li; Yandong Ma; et al. (CATENA, 2026)

Altered gray matter network segregation and disrupted interregional connectivity in children with persistent developmental stuttering: a graph-theoretical morphometric study - Wanqing Liu; Dan Ma; Chuanlong Cao; Sai Liu; XinMao Ma; Fenglin Jia; Pei Li; Hui Zhang; Yimin Hua; Yi Liao; Haibo Qu (Brain Imaging and Behavior, 2026)

The impact of cumulative obesity and genetic susceptibility on biological aging in Chinese older adults - Jiening Yu; Liming Zhang; Zhenqing Yang; Xueqing Jia; Ciyun Zhao; Jiaxin Liu; Jingyun Zhang; Xingqi Cao; Yinyi Song; Lu Li; Xuehui Sun; Hui Zhang; et al. (GeroScience, 2026)

Tracking Eastward Displacement of Pacific Saury Fishing Grounds Using Nighttime Fishing Radiance: The Role of Early‐Season Kuroshio Extension Variability - Hao Tian; Hiroto Abe; Yang Liu; Bingqing Chen; Bin Kang; Jianchao Li; Sei‐Ichi Saitoh; Chang Cao; Wenjia Li; Hui Xu; Shuyang Ma; Yongjun Tian (Fisheries Oceanography, 2026)
Pacific saury ( Cololabis saira ) is an ecologically and commercially important small pelagic species in the northwestern Pacific, where fishing grounds have shifted markedly eastward in recent years. However, the role of early‐season oceanographic variability in shaping this redistribution remains poorly understood. Using catch records, Automatic identification systems‐derived fishing hours, vessel registry data, and nighttime light (NTL) observations, we examined fishing activity during 2012–2020 and linked fishing‐ground displacement to environmental variability and Kuroshio Extension system (KES) hydrographic conditions. NTL radiance outperformed CPUE and fishing hours in representing environmentally structured fishing‐ground variability, highlighting its value for tracking transboundary displacement in this light‐luring fishery. The optimal random forest model identified mixed layer depth, sea surface salinity, phytoplankton carbon, and sea surface temperature (SST) as the dominant predictors. Radiance‐weighted centers of gravity revealed especially strong eastward displacement in 2019–2020. Early‐season (May–July) displacement was strongly associated with annual displacement, indicating that the annual fishing‐ground pattern was largely preconditioned during the early‐season. Among the dominant environmental variables, SST displacement in the traditional fishing grounds showed the strongest relationship with the eastward shift. Years with longer Kuroshio Extension fronts and higher regional mean KE showed greater eastward displacement, indicating an association between early‐season KES‐related hydrographic variability, thermal reorganization of the traditional fishing grounds, and eastward redistribution. These findings demonstrate the value of nighttime fishing radiance for detecting environmentally structured fishery redistribution and suggest that early‐season KES‐related hydrographic variability is an important oceanographic context for the recent eastward shift of saury fishing grounds.

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Sedimentary evolution and its response to climate and sea level changes in the northern South China Sea over the past 60 ka - Kairui Liu; Kaikai Wu; Hui Zhang; Peng Cao; Xiaoyan Li; Lin Jia; Kunshan Wang; Lina Ai; Hongmin Wang; Shengfa Liu (Quaternary International, 2026)

Atmospheric bulk deposition of microplastics in Jiuzhaigou World Natural Heritage Site: Tourism-associated divergence between particle number and polymer mass fluxes - Ting Liu; Yunqian Chen; Weiyang Xiao; Lv Zhou; Yutao Cao; Philip K. Hopke; Dongmei Liu; Jiangbin Shu; Hui Liu; Rongqiu Li; Xue Qiao (Journal of Hazardous Materials, 2026)

Intrasporangiaceae-linked autotrophic Cr(VI) reduction coupled with sulfur oxidation in deep paddy soil revealed by DNA-stable isotope probing and metagenomics - Hao Zhang; Miaomiao Zhang; Baoqin Li; Feiyan Yao; Weimin Sun; Haiming Zhao; Xiaoxu Sun; Xunwen Chen; Yubo Cao; Hui Li (Journal of Environmental Sciences, 2026)

Seasonal-Spatial Hydrochemical Variations and Salinity Control Mechanisms of Shallow Groundwater: Insights from the Northern Piedmont of the Qinling Mountains, China - Yixin Liu; Hui Qian; Panpan Xu; Xiaoxin Shi; Siqi Li; Yanyan Gao; Weijie Zhao; Shuhan Yang; Zhiming Cao; Jie Chen; Yanjun Shen (Journal of Environmental Sciences, 2026)

Chemical weathering processes in the north-south transition zone of China: A case study from the Danjiang River Basin - Zhiming Cao; Hui Qian; Yanyan Gao; Kang Li; Panpan Tian; Weijie Zhao; Shuhan Yang; Xiaoxin Shi; Siqi Li; Yixin Liu; Puxia Wu; Yandong Ma (Journal of Environmental Sciences, 2026)

Simultaneous enantioselective determination of 30 chiral pesticides in vegetables: enantiomeric composition, separation, and absolute quantification using LC-MS/MS - Tianyue Zhao; Xin Jiang; Yingjie Zhu; Danning Shen; Chunzheng Li; Danli Liu; Hui Li; Yanqing Cao; Kun He; Na Wang (Food Chemistry, 2026)

Environmentally responsible synthesis of polymer-nano fused composite membranes with long-term stability for sustainable CO2 separation - Hui Shen Lau; Fan Feng; Qiubo Chen; Xue-Li Cao; Shi-Peng Sun; Wai Fen Yong (Chemical Engineering Journal, 2026)

Click-crosslinked nano-hydrogel enables metabolic immune reprogramming for diabetic foot ulcers - Heng Gong; Tingjiang Gan; Xikun Ma; Ye Wu; Yaxing Li; Shijiu Yin; Biao Cao; Xiangtian Deng; Cheng Zheng; Yunbing Wang; Hui Zhang (Science China Life Sciences, 2026)

TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Biomolecular condensates from a short peptide for enhancing radiotherapy via spatial sequestration of PARP1 - Xiaoyao Cai; Yipeng Cao; Hui Li; Wei Xu; Yanbin Chen; Chaoyi Lyu; Zhiyong Yuan; Yumin Zhang; Jianfeng Liu; Cuihong Yang (Science Bulletin, 2026)

Evolution of upwelling in the southwestern Sumatra waters since the middle Holocene: Evidence from mineralogy and geochemistry - Xue Li; Lina Ai; Hui Zhang; Peng Cao; Lin Jia; Xiaoyan Li; Kunshan Wang; Kaikai Wu; Hongmin Wang; Rainer Arief Troa; Rina Zuraida; Eko Triarso; et al. (Quaternary International, 2026)

Assessing coastal groundwater risks from nuclear-contaminated water discharge under extreme drought and sustainable recharge solutions - Jiao Zhang; Yaqiang Wei; Yuling Chen; Zhenzhong Hu; Damià Barceló; Tian-Chyi Jim Yeh; Jiazhong Qian; Bradley A. Weymer; Zi Zhan; Xinde Cao; Hui Li (Journal of Contaminant Hydrology, 2026)

Multi-marker UPLC-MS/MS detection of sesame, soybean, and peanut oil adulteration in camellia and olive oils: a high-sensitivity approach for food authenticity - Nan Deng; Hui Wang; Fangping Yin; Xiaobo Hu; Jijun Qin; Feifei Zhong; Ben Li; Wenting Cao; Peng Zhou (Food Chemistry, 2026)

Mechanic simulation of aquatic biodisturbation enhances phosphorus uptake and lead immobilization in paddy soils - Hui Gao; Qingnan Chu; Jun Wang; Detian Li; Jin Zhou; Wenya Hao; Min Zhang; Yumei Mao; Linkui Cao; Chengming Zhang; Zhimin Sha (Journal of Soils and Sediments, 2026)

Self-amplifying ROS nanoplatform with dual responsiveness for tumor-targeted photodynamic therapy - Yiping Zhou; Zhongjian Wang; Ning Tong; Hui Cao; Zhenya Sun; Lixue Chen; Ning Wang; Lei Li; Ran Cui; Lu Liu; Han Bao (Journal of Pharmaceutical Investigation, 2026)

A Study on the Suitability of Operating Strategies for PV/T-Medium-to-Deep-Ground-Source Heat Pump Heating Systems Based on Peak-and-Off-Peak Electricity Rates - Dong Wei; Yu-ping Zhang; Quan-hui Liu; Yi-chao Zhao; Hao Wu; Sheng-ji Xu; Yu Cao; Jia-yuan Li; Ling-ling Bao (Applied Geophysics, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Regional immunity in the respiratory tract: challenges and opportunities - Shuo Wang; Si Chen; Lianpan Dai; Fengqi Li; Hui Li; Kefang Liu; Xiangzhi Meng; Jian Wang; Hua Yue; Airu Zhu; Bin Cao; Ling Chen; et al. (Science Bulletin, 2026)

Ammonium ion-assisted electrodeposition of CuBi2O4/NiO photocathodes for efficient photoelectrochemical desalination - Shengbo Yuan; Min Luo; Wenbo Zhou; Jianrong Li; Yue Cao; Kwan San Hui; Yi Yang; Yang Wang; Xiaoman Li; Yongqing Yang; Fuming Chen (Desalination, 2026)

Modern sediment sources and transport processes in the southern Arabian Sea: Evidences from geochemistry and mineralogy - Xiaoyan Li; Bingjie Sun; Kaikai Wu; Peng Cao; Hui Zhang; Kunshan Wang; Lina Ai; Hongmin Wang; Zhengxin Yin; Liang Chen; Shengfa Liu (Continental Shelf Research, 2026)

Xerophilusin B attenuates wear particle: associated osteolysis by inhibiting NF-κB signaling and restoring osteoblast–osteoclast coupling - Hui Shi; Qian Meng; Tao Meng; Changling Du; Chuang Xu; Heng Cao; Kefan Zhang; Jian Li (Journal of Molecular Histology, 2026)

Non-targeted metabolomics coupled with simulated processing strategy reveals temperature-driven flavonoid and organic acid transformations in Typhae pollen - Fang Tian; Mingqi Chen; Ying Zhang; Hui Cao; Menghua Wu; Jinju Zhang; Hanpeng Jiang; Wen Li; Zhiguo Ma (Food Research International, 2026)

Evaluation of gamma irradiation on the microbiological, phytochemicals, and aromatic profiles of sun-bleached preserved pepper (Capsicum annuum L.) - Mengyun Ouyang; Sheng Cao; Yiji Zhou; Mo Mo; Yuanfang Xu; Qiling Zhang; Yong Zhang; Chao Deng; Feng Guo; Hui Song; Yan Wang; Yiqun Huang; et al. (Food Chemistry, 2026)

In-site fabrication of pheromone-loaded core-sheath fibers via handheld emulsion electrospinning with natural surfactants for Apolygus lucorum attraction - Hai-yan Ye; Wen-jie Shangguan; Han Wu; Jing Zhao; Liu-bin Xiao; De-jin Xu; Guang-chun Xu; Qi-liang Huang; Guo-hui Zhang; Li-dong Cao; Yong-an Tan (Chemical Engineering Journal, 2026)

CHiC gene positively regulates the resistance to Botrytis cinerea in Arabidopsis - Xi Wu; Xin Yu; Shuxun Xu; Shuangyao Li; Jing Zhang; Guangna Chen; Qian Ma; Shuqing Cao; Hui Song (Plant Cell Reports, 2026)

Dynamics and biophysical regulation of evapotranspiration in winter wheat/summer maize rotation farmland in alluvial/sedimentary sand land in the ancient course of Yellow River - Xiaojuan Ren; Guodong Li; Xuejian Sun; Li Ma; Hui He; Qingtao Zhao; Longsheng Wang; Yunfei Gong; Bingqian Han; Chenxi Cao (Irrigation Science, 2026)

B cell-driven immune remodeling in inflammatory bowel disease: links to pathogenesis and therapeutic failure - Guomin Li; Hui Cao; Jiemin Hong (Inflammation Research, 2026)

Ternary network derived from polyphenol-inspired sticky nanoparticle: nanofiltration separation efficiency and end-of-life membrane regeneration potential - Jiaying Yan; Panpan Wang; Ying Cao; Jinlong Zhu; Xingyan Jin; Luwei Li; Chuandong Wu; Hao Zhang; Hui Xie; Jun Ma (Water Research, 2026)

Recent advances in metal-phenolic networks for delivery and removal: properties, applications, and future perspectives - Xin Zhang; Ikram Alouk; Hui Liang; Guangjian Li; Yutao Wang; Yufei Cao; Wen-Yong Lou (Trends in Food Science & Technology, 2026)

Cissatriterpenoids D-L, nine undescribed polyhydroxylated oleanane triterpenoids from Cissampelos pareira var. hirsuta - Shuang-Qin Cao; Ru-Yi Pan; Tong-Tong Zhang; Jian-Hong Gong; Meng Li; Hui Chen; Jing-Ke Zhang; Zhi-You Hao; Xiao-Ke Zheng; Yan-Jun Sun; Wei-Sheng Feng (Phytochemistry, 2026)

Poly(deep eutectic solvent)@MOF-801 for technical surveillance of carbaryl: Pesticide residue safety control strategy - Xicheng He; Yumin Yang; Ying Cao; Ziming Wang; Haixiang Li; Zhiliu Liu; Yan Wang; Fengyun Li; Qian Zhang; Abdulla Yusuf; Feiran Li; Mi Hu; et al. (Journal of Environmental Management, 2026)

Preparation of synthetic graphite from coal-based humic acid by catalytic graphitization as high-performance anode materials for lithium-ion batteries - Saidan Zhao; Baolin Xing; Yongzhi Liu; Hui Guo; Huihui Zeng; Xiaoxiao Qu; Song Cheng; Feng Shi; Chuanxiang Zhang; Yaowen Xing; Yijun Cao; Peng Li (Fuel, 2026)

Enhanced metal-organic framework-driven deep learning-assisted magnetic crystal paper aptsensor for two-step sensitization and in-situ detection of pathogenic bacteria - Lulu Cao; Yuwei Ren; Shengshi Jiang; Hui Li; Maoling Hu; Xin Zhang; Xiaoyu Yu; Weichao Wu; Mengyu Li; Zhao Liang; Na Ling; Hongzhou Chen; et al. (Chemical Engineering Journal, 2026)

City-scale assessment of green-roof carbon: high-frequency chamber fluxes and district inventories reveal microclimate-driven sinks and seasonal resilience - Feilong Shen; Zhenzhu Cao; Chongyang Zhang; Ying Zhao; Hui Li; Shiliang Liu; Guiying Jiang; Jiawei Yang; Fang Liu (Building and Environment, 2026)

A quantitative assessment of the state and evolution of city–lake relationships using a symbiosis model in the Taihu Lake Basin - Pingxing Li; Hui Cao; Hongguang Liu; Jiang He (Journal of Geographical Sciences, 2026)

Metallogenic Age of the Qianjiadian Uranium Deposit—Evidence from Fluid Inclusions and (U-Th)/He - Ruxin Ding; Yangshijia Li; Zilong Li; Rongli Huang; Minqiang Cao; Xingzhou Chen; Hui Rong; Heping Zou (Journal of Earth Science, 2026)

Lake Water Depth and Nutrient Gradients Mediate Aquatic Plant Distribution via the Strength of Trait Network Associations - Guixiang Yuan; Huan Long; Jun Liu; Qiling Xie; Yaoxuan Tan; Zihui Hong; Jiahui Yue; Aimin Zhou; Hexuan Zhou; Weilin Xu; Bao Wang; Huanyao Liu; et al. (Global Change Biology, 2026)
Aquatic macrophyte responses and adaptation to water depth and nutrient gradients are of critical importance for understanding the functional ecology of lakes and their restoration when degraded. However, the role of plant trait networks (PTNs), a powerful tool for decoding trait–environment–function relationships, in mediating these adaptations remains unclear, particularly across species and community scales. We conducted cross‐scale PTN analyses at species and community levels for aquatic macrophytes, integrating assessments of phylogenetic signals and hierarchical environmental filtering. At species level, aquatic macrophytes exhibited two complementary PTN‐based adaptive strategies: trait compartmentalization to enhance stress tolerance and trait integration to optimize resource utilization. Notably, local environmental conditions (rather than phylogenetic signals) dominated the pattern of PTN metrics, highlighting the primacy of immediate habitat constraints over evolutionary relatedness in driving species‐specific adaptations. At community level, environmental filtering operated hierarchically, acting sequentially by water depth, nutrient availability, and lake morphology. PTNs further mediated the trade‐off between community diversity and productivity, providing a mechanistic link between abiotic filtering and ecosystem function. Our findings advance network theory in functional ecology by extending its application to aquatic systems, bridging longstanding gaps between terrestrial and aquatic PTN research, and offering actionable guidance for eutrophic lake restoration (e.g., by targeting PTN‐linked core traits related to nutrient adaptation). Overall, our work provides a cross‐scale framework for understanding PTN mediated adaptation of aquatic macrophytes and its implications for ecosystem management.

Decumbic acid derivatives from soil fungus Lasiodiplodia sp. BG1083 - Hong-Qiao Dai; Xiao-Bing Su; En-Tao Zhou; Wen-Ting Li; Shuang-Shuang Chen; Hui-Yang Cao; Lin Hu; Meng-Yuan Jiang (Natural Product Research, 2026)

Applicability assessment of molecular tools and identification of lines suitable for genetic transformation in the red alga Pyropia yezoensis - Xuexue Cao; Jiaxin Qu; Jia hui Sun; Yichi Li; Ying Sun; Yunxiang Mao; Fanna Kong (Algae, 2026)
Pyropia yezoensis, a red macroalga distributed in the intertidal zone, serves as an important model organism for studying the adaptive mechanisms of intertidal seaweeds in response to abiotic stressors. Additionally, it is a significant economic seaweed due to its high nutrient content and is widely cultivated in China, Japan, and Korea. Despite its importance, existing molecular tools for genetic transformation remain limited and require further development to enhance our understanding of P. yezoensis biology. To address this limitation, based on previous studies, we firstly evaluated the expression of eight fluorescent proteins (FPs) in P. yezoensis. Our findings confirmed that PyZsYellow, PyZsGFP, and PysGFP can be detected successfully their specific fluorescent signals within the cells of P. yezoensis thalli. Notably, PyZsGFP demonstrated effectiveness in sporophytic filaments. 2×SV40 and PyNP may function as nuclear localization signal sequences, effectively directing the FP to localize within the nucleus of cells in P. yezoensis. T2A linker can mediate protein cleavage, to express the multiple genes in one construct, enabling them to function independently in P. yezoensis. Furthermore, we identified that the RZ line exhibited the highest transformation potential, while the middle region of thalli showed the superior transformation efficiency. A significant correlation between cell size and transformation efficiency. These findings will contribute to developing a systematic toolkit for conducting genetic transformations and elucidating gene functions in P. yezoensis.

Coordination-tailored conductive metal-organic frameworks boost CO2 electroreduction to ethylene for cascade ethylene glycol production - Hui Guo; Shao-Shuai Zhao; Duan-Hui Si; Weijin Li; Zi-Ao Chen; Rong Cao; Roland A. Fischer; Yuan-Biao Huang (Science Bulletin, 2026)

A large-scale framework for deriving tidal flat topography from SWOT data - Hao Xu; Nan Xu; Wenyu Li; Kai Tan; Chunpeng Chen; Huan Li; Lucheng Zhan; Pei Xin; Jiaqi Yao; Peng Li; Zhen Zhang; Haipeng Zhao; et al. (Remote Sensing of Environment, 2026)

Genomic insights into stepwise selection reshaping fruit traits and male-biased selection driving hermaphroditism in papayas - Changmian Ji; Ruizong Jia; Yuliang Zhang; Xiaoxi Du; Xueying Huang; Huiliang Li; He Dai; Yu Wang; Qian Jiang; Zhengnan Xie; Shanshan Huo; Yang Cao; et al. (Molecular Plant, 2026)

Bio-template synthesis of graphitized carbon-decorated Fe2O3 hierarchical tubes for high-response and low-temperature H2S detection - Ming-Yan Cao; Hui-Nan Lei; Hui-Ye Jiang; Ya-Nan Li; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2026)

Biomineralization induced by Shigella dysenteriae JS3: The mechanism, and the differences between biotic and abiotic whewellite and struvite - Na Guo; Jizheng Qiao; Shuhua Zhang; Shengzhe Gao; Yanhong Zhao; Chao Han; Hui Zhao; Yanyang Zhao; Xiao Gao; Ruirui Meng; Bin Cao; Yu Li; et al. (Chemical Geology, 2026)

Corrigendum to “Separation and purification of N-acetylglucosamine from the fermentation broth of corynebacterium glutamicum by electrodeionisation method” [Biomass Bioenergy 202 (2025) 108165] - Xiqin Zhou; Hao He; Minxuan Wang; Zemin Li; Jie Wei; Gaojie Pan; Hui Cao; Tianwei Tan (Biomass and Bioenergy, 2026)

Endothelial GATAD1 Exacerbates Blood-brain Barrier Dysfunction in Ischemic Stroke through Caveolae-mediated Transcytosis - Lizhen Fan; Hui Liu; Shanshan Li; Lingling Li; Zhi Zhang; Pinyi Liu; Haiyan Yang; Shengnan Xia; Xiang Cao; Chun Wang; Yun Xu (Neuroscience Bulletin, 2026)

Hydrochemical evolution and surface water-groundwater interactions in a typical mountainous basin: Insights from multiple isotopes, chemical tracers, and multiple models - Zhiming Cao; Hui Qian; Yanyan Gao; Kang Li; Xiaoxin Shi; Siqi Li; Panpan Tian; Yixin Liu; Jinkun Zhang; Zeyu Shi; Puxia Wu; Yandong Ma (Journal of Environmental Chemical Engineering, 2026)

AIEgen-regulated metal-organic framework enabled machine learning-assisted lateral flow immunoassay sensor for intelligent diagnosis of P. aeruginosa - Tiemei Li; Jinbo Cao; Yao Wang; Hui Chen; Shaobin Gu; Xinzhong Li (Chemical Engineering Journal, 2026)

Unlocking efficient Cr(Ⅵ) bioremediation in Zobellella denitrificans Y1 via Cu(Ⅱ)-mediated redox cycling: From genomic insights to non-enzymatic reduction pathway - Shuai Gao; Shuzhen Li; Shuangfeng Cao; Jing Lu; Qi Guo; Hui Zhong; Zhiguo He (Bioresource Technology, 2026)

Spatiotemporal characteristics, drivers, sources, and health risks of nitrate and sulfate in groundwater on the Chinese Loess Plateau - He Su; Yutong Zhang; Wengeng Cao; Yanrong Li; Hui Zhang; Zhi Li; Lisha Ma (Water Research, 2026)

A waste-free segmented roasting strategy for sustainable recovery of critical metals from spent Indium-Gallium-Zinc oxide - Xuan He; Baozhong Ma; Yubo Liu; Xiang Li; Zhihe Cao; Hui Yang; Chengyan Wang (Waste Management, 2026)

Mid-late Holocene environmental change and social resilience in Central Plains of China: Evidence from Sha-Ying Rivers floodplain - Wei Li; YiHsien Lin; Linjing Liu; Xiaochen Pei; Ligang Zhou; Yanpeng Cao; Chen Liu; Hui Wang; Peng Lu; Yijie Zhuang; Meilin Guo; Fawei Liang; et al. (Quaternary Science Reviews, 2026)

A fluorescent probe based solid-state fluorophore for the detection of N2H4 and its application in environmental samples - Cong-Ping Cao; Qian Song; Chu-Yu-Hui Peng; Shuang-Xian Li; Guo-Jiang Mao; Juan Ouyang; Liufang Hu; Yongfei Li; Chun-Yan Li (Journal of Hazardous Materials, 2026)

Key toxicological targets identification for atherosclerosis induced by environmental hazardous substance nicotine exposure and its antagonists screening from active components of Dendrobium officinale - Heng Li; Yuhan Zhang; Qianqian Wang; Liwei Li; Guangzhen Zheng; Ruli Zheng; Tianjing Wang; Xiaoyao Yang; Zimeng Shi; Fengjiu Yang; Haiwei Kuai; Lijuan Cao; et al. (Journal of Hazardous Materials, 2026)

Study on the effect of ethylene oxide fumigation on the colonies of unearthed wooden cultural relics - Hui Li; Zeyu Pan; Chuan Yang; Meng Sun; Hui Jiang; Buyu Cao; Xingxia Ma (International Biodeterioration & Biodegradation, 2026)

Investigate the in-plane and out-of-plane elastic properties of spiderweb-inspired hierarchical composite honeycombs using forward analytical and inverse numerical approaches - Peng-Xu Lu; Jun Wang; Jin Zhou; Zhou Qiao; Jichuan Cao; Hui Li; Feiping Du; Zhongwei Guan (Engineering Structures, 2026)

Ion-dipole interactions regulated interface for stable high-depth of discharge Zn anode - Pengyan Jiang; Xiaobin Hui; Yuyang Yi; Renjie Li; Jingya Yu; Feiyang Chen; Liucheng Cao; Chi Fai Cheung; Kai Qi; Bao Yu Xia; Zheng-Long Xu (Chemical Engineering Journal, 2026)

Gastrodin improves learning and memory in sleep-deprived mice through suppression of ferroptosis in hippocampal neurons via Nrf2 - Yin Cao; Xuanxuan Huang; Yi Wu; Mingrui Li; Yuping Miao; Hui Wu; Hongfei Wu; Zhengtao Wang; Xiaojun Wu; Zipeng Gong (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

miR-133b-3p Mitigates D-Galactose-Induced Hippocampal Neuron Aging Through Autophagy Regulation via the MAPK/ERK Signaling Pathway - Yang Cao; Chen Zhao; Jiaxin Li; Qiang Gao; Chunmei Lv; Jiao Wang; Na Qiang; Wenwen Zhang; Huiyu Su; Xinyu Min; Jinfeng Liu; Xiaoqi Dai; et al. (Molecular Neurobiology, 2026)

Automatic Image Co-registration of Carotid Angiography and Intravascular Optical Coherence Tomography Based on Machine Learning Method: A Pilot Feasibility Study - Hui Xu; Jia-Nan Li; Yan Xu; Jun-Ren Ma; Kang Zong; Rui Zhu; Yi-Hui Cao; Peng-Fei Yang; Rui Zhao; Jian-Min Liu (Annals of Biomedical Engineering, 2026)

Hydrological imbalance in Nam Co Lake, the third-largest lake on the Tibetan Plateau - Wenhao Ren; Hui Qian; Shiqiao Zhou; Yanyan Gao; Yaoming Ma; Zhongbo Su; Weiqiang Ma; Zhiming Cao; Weijie Zhao; Kang Li (Journal of Hydrology, 2025)

Oxidizing radical-induced transformation of halogenated bisphenol compounds in water: Kinetics and mechanisms - Yuhang Li; Zhantu Ye; Shiqing Qiu; Guodong Li; Hui Cao; Lijun Niu; Mingbao Feng (Journal of Environmental Chemical Engineering, 2025)

Bioinspired Nacre-layer composite loose nanofiltration membranes: Preparation and performance evaluation - Junpeng Mao; Peng Liu; Ning Tang; Hui Li; Yaxin Gu; Yunwu Yu; Yunxue Liu; Lihua Wang; Ji Cao (Journal of Environmental Chemical Engineering, 2025)

High internal phase Pickering emulsions stabilized by arginine-myosin microgel particles for 3D printing low salt surimi - Quanhong Lu; Jun Yang; Yunuo Zhou; Yuan Xu; Fawen Yin; Yanfu He; Hui Ye; Hesham El-Seedi; Longteng Zhang; Qian Li; Jun Cao; Chuan Li (Food Chemistry, 2025)

Photothermal synergistic catalysis on Zr-doped ZnIn₂S₄ for mild alcoholysis of epoxides: Atomic-level acidity-basicity modulation and carrier dynamics steering - Bin Zhu; Jiulin Tang; Qichao Cao; Nan Zhang; Xiaoan Yu; Kaisheng Zhang; Hui Du; Zhuo Li; Yanhua Peng; Ruitong Gao; Haoyuan Cai; Xue-fang Yu; et al. (Chemical Engineering Journal, 2025)

Phosphorus incorporation in cobalt molybdate: Controlling Mo leaching for surface reconstruction to improve hydrogen evolution - Juanjuan Wang; Yuxuan Xiao; Jinxian Feng; Chunfa Liu; Lun Li; Youpeng Cao; Chengcheng Zhong; Ziwen Feng; Wendi Zhang; Zhi-Quan Liu; Hui Pan (Chemical Engineering Journal, 2025)

Recombinant Expression of a New Antimicrobial Peptide Composed of hBD-3 and hBD-4 in Escherichia coli and Investigation of Its Activity Against Multidrug-Resistant Bacteria - Nianzhi Ning; Han Yan; Binwang Cao; Wenjing Yu; Liangyan Zhang; Deyu Li; Tao Li; Xingxiao Zhang; Hui Wang (Probiotics and Antimicrobial Proteins, 2025)

Geochemical Compositions and Transport Patterns of Surface Sediments from the Malacca Strait - Lina Ai; Shengfa Liu; Hui Zhang; Peng Cao; Xue Li; Wenjing Qi; Kaikai Wu; Che Abd Rahim Mohamed; Xuefa Shi (Journal of Ocean University of China, 2025)

The CMA Global Atmospheric Reanalysis Version 1.5 (CRA1.5) - Tao Zhang; Zijiang Zhou; Zhiquan Liu; Chunxiang Shi; Shuang Yao; Lipeng Jiang; Yan Yao; Zhisen Zhang; Xiao Liang; Zhiqiang Zhang; Junxia Gu; Jie Liao; et al. (Journal of Meteorological Research, 2025)

Synergistic effects of biochar and organic fertilizer on root exudates, microbial community, and yield in dry direct-seeded rice - Xiaoqiang Cao; Deping Liu; Jilong Liu; Lingling Zhang; Mo Li; Guoxin Shi; Hui Liu; Hao Wang; Weili Sun (Applied Soil Ecology, 2025)

Deep learning-based tunnel advance geological forecast for polygon targets via regional GPR data - Ting-wei Yang; Jing-he Li; Ye-hui Cao; Bin Xiong; Liu-ye Wei (Applied Geophysics, 2025)

Investigation of the Alterations in the Gut Microbiota and Intestinal Mucosa in Mice Infected with Echinococcus multilocularis - Deping Cao; Wenjun Huang; Mingquan Pang; Jiajing Li; Haitao Huang; Hui Ma; Dayu Li; Yufei Qin; Xiaohong Peng; Haining Fan (Acta Parasitologica, 2025)

Research on the Reinforcement Effect of the Elephant-Foot Method in Aeolian Sand Tunnels - Ji-hua Qin; Xi-peng Li; Ya Wang; Xiao-li Cao; Dong Li; Yi-guo Xue; Fan-meng Kong; Hui-min Gong; Bang-xiang Li; Chao Lu; Guang-kun Li (Applied Geophysics, 2025)

Flash roasting for phase transformation of α-spodumene coupled with sulfuric acid pressure leaching to enhance lithium extraction - Dongqi Song; Wei Chen; Qingkang Yan; Yu Liu; Ge Kuang; Hui Guo; Guosheng Li; Yijun Cao (Minerals Engineering, 2025)

Atomic-shell engineering in manganese-doped palladium@iridium nanozymes: d-Band optimization for enhanced peroxidase-like activity in ultrasensitive lateral flow immunoassays - Ting Tan; Qianqian Cao; Ming-Hui Duan; Junmin Li; Yafeng Xie; Min Tan; Xiwu Yin; Jikai Wang; Weiguo Wang (Chemical Engineering Journal, 2025)

Delayed fluorescence material-assisted for achieving high performance layer-by-layer organic solar cell with extended exciton lifetime and improved film morphology - Xiaoyang Du; Jinglong Chen; Zhengyu Guo; Luye Cao; Xinrui Li; Hui Lin; Gang Yang; Caijun Zheng; Silu Tao (Chemical Engineering Journal, 2025)

A hydrophobic and zincophilic protective layer for highly reversible Zn metal anodes - Chunyan Cao; Zhu Xu; Haoyang Li; Kexuan Wang; Ruiqing Li; Huibo Wang; Huilong Dong; Wei Zhang; Hui Liu; Shi Chen; Bin Fei; Mingzheng Ge (Chemical Engineering Journal, 2025)

Separation and purification of N-acetylglucosamine from the fermentation broth of corynebacterium glutamicum by electrodeionisation method - Xiqin Zhou; Hao He; Minxuan Wang; Zemin Li; Jie Wei; Gaojie Pan; Hui Cao; Tianwei Tan (Biomass and Bioenergy, 2025)

Recipient Periodic Fasting Promotes Osteogenesis of Implanted Mesenchymal Stromal Cell Aggregates and Safeguards Diabetic Mandibular Bone Regeneration - Zi-Qi Zhang; Yuan Yuan; Xiao-Hui Zhang; Jia-Ning Liu; Yuan Cao; Lu Liu; Lu-Fan Yang; Yi-Han Xiao; Shan-Shan Huang; Bing-Dong Sui; Jian-Fei Liang; Ji Chen; et al. (Stem Cell Reviews and Reports, 2025)

An optimal sequential physical retrieval system for retrieving high-accuracy diurnal atmospheric gases from FY-4B/GIIRS: Theory, algorithm and evaluation - Zhenxing Liang; Dasa Gu; Xin Li; Zijie Xu; Xiangyunong Cao; Heming Bai; Rui Li; Chengxing Zhai; Hui Su; Alexis K.H. Lau (Remote Sensing of Environment, 2025)

High efficacy of (Z)-ligustilide in inhibiting postharvest apple ring rot and its antifungal mechanism against Botryosphaeria dothidea - Xiao-Yi Tong; Li-Li Song; Hui-Fang Du; Ya-Hui Zhang; Jia-Wen Shou; Cai-Juan Zheng; Wen-Bin Gao; Zhong-Cheng Liu; Du-Qiang Luo; Yun-Feng Liu; Fei Cao (Postharvest Biology and Technology, 2025)

Calibration and application of brGDGT-based temperature parameters in the twilight zone of the South China Sea - Aamir Ali; Jiantao Cao; Chao Huang; Hui Li; Guodong Jia (Global and Planetary Change, 2025)

Antibacterial mechanism of non-thermal treatments against Pseudomonas putida and their application in tilapia fillets - Dongyin Liu; Zhiliang Huang; Yuan Xu; Xin Zhang; Hui Ye; Xiaoshuan Zhang; Longteng Zhang; Yanfu He; Jun Cao; Jiamei Wang; Jun Yang; Chuan Li (Food Research International, 2025)

Biomimetic seaweed photonic graphene for high-performance broadband, self-powered, and polarized image photodetectors - Shanshui Lian; Jinqiu Zhang; Fanghao Zhu; Genqiang Cao; Hui Ma; Zhenghao Xu; Wenwu Xu; Li Zheng; Jiayun Dai; Gang Wang (Chemical Engineering Journal, 2025)

Interfacial polarization and lattice hydrogenation enable accelerated aluminum combustion with hydrogen-rich fluoropolymers - Chuang Yao; Qingguan Song; Li Meng; Haoyuan Zhong; Wei Cao; Hui Li; Chang Q. Sun; Siping Pang; Lei Zhang (Chemical Engineering Journal, 2025)

Reestablished buried interface by multifunctional additive for high-efficiency perovskite solar cells - Xiaoli Zhang; Fobao Xie; Bing’e Li; Xinghan Zeng; Chuangping Liu; Qinghua Cao; Jiangping Xing; Eugene Troyan; Baihong Zheng; Hui Liu; Andrey Stepanov (Chemical Engineering Journal, 2025)

Sediment redox state threshold for N2O emissions and indirect regulatory impact of organic carbon in shallow lakes - Hui Li; Huatang Deng; Yingying Cai; Jianfen Li; Zhenhua Qin; Fangyuan Chen; Xiuyun Cao; Chunlei Song; XinBin Duan (Journal of Soils and Sediments, 2025)

Rice-duck farming enhances phosphorus use and grain yield via altering soil phosphorus fractions in the Yangtze River Delta of eastern China - Hui Gao; Qingnan Chu; Xiangyu Liu; Liang Zheng; Shuhan Xu; Linkui Cao; Detian Li; Shuai Yin; Ping He; Chengrong Chen; Zhimin Sha (Agriculture, Ecosystems & Environment, 2025)

Nitrogenous fertilizers affect Cd accumulation in the soil-mulberry-silkworm system: implications for safe utilization of contaminated farmland - Yongbing Jiang; Xiyun Yang; Shimeng Jiang; Armel Tientega; Hui Cao; Zhangbao Li; Ming Wang; Renzhi Huang; Tangzhong Long (Environmental Monitoring and Assessment, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

AhR-mediated histone lactylation drives cellular senescence during benzo[a]pyrene-evoked chronic obstructive pulmonary disease - Li-Hong Chen; Jun-Ping Wei; Meng-Die Li; Xiu Lu; Yi-Cheng Ma; Yu Wang; Ling Zheng; Jun Fei; Wei Cao; De-Xiang Xu; Jin Yang; Hui Zhao; et al. (Journal of Hazardous Materials, 2025)

Identifying nitrate pollution of groundwater based on aquifer vulnerability and surface nitrogen loads in the Northern Foot of the Qinling Mountains, China - Yixin Liu; Hui Qian; Yanyan Gao; Siqi Li; Xiaoxin Shi; Zhiming Cao; Qi Long; Yi He; Yandong Ma; Puxia Wu; Yanjun Shen (Journal of Hazardous Materials, 2025)

Effect of blanching times and drying temperatures on the color, moisture migrations, microstructures, phytochemicals, and flavors of chili pepper (Capsicum annuum L.) - Yongkang Xie; Junjun Geng; Ping Li; Yan Zhao; Junhao Han; Hui Yang; Shina Cao (Food Chemistry, 2025)

The oral delivery of avenanthramide-C encapsulated by barley self-assembly peptides reduces high-fat diet-induced brain oxidative stress and inflammation - Li Sen; Wanqing Cao; Ze Zhang; Qianqian Wang; Hongdong Song; Hui-Min David Wang; Xiao Guan (Food Bioscience, 2025)

Diaporthein B/ZnO/chitosan biodegradable film for postharvest preservation of apples: Characterization and application - Hui-Fang Du; Fei Cao; Zhi-Hong Xu; Ya-Xian Gao; Ya-Hui Zhang; Sen Pang; Wan Li; Long-Fei Li; Li Han; Li-Juan Wang; Hong-De An (Food Packaging and Shelf Life, 2025)

Daily runoff simulation in humid regions using the entropy-weighted ensemble learning models - Zhenyu Tang; Liping Zhang; Chen Hu; Yaze Li; Gangsheng Wang; Zhiling Zhou; Xiao Li; Zhengfeng Bao; Hui Cao; Benjun Jia (Environmental Modelling & Software, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Dissipation of penthiopyrad in polyethylene microplastics coexisting soils: Roles of soil properties and microbial communities - Miqi Li; Hui Liu; Kexin Zhang; Chengjie Lian; Xintong Wang; Danyang Zhao; Yunqi Cao (Pesticide Biochemistry and Physiology, 2025)

Sex-and stage-specific effect of prenatal exposure to organophosphate esters with children's physical growth patterns and adiposity rebound timing: Modification by breastfeeding - Xing Wang; Juan Tong; Han Li; Mengjuan Lu; Yuan Liu; Hong Gan; Yifan Wang; Menglong Geng; Xuejiao Qie; Xiulong Wu; Hui Gao; Beibei Zhu; et al. (Journal of Hazardous Materials, 2025)

Experimental study on shear behavior of rough fractured granite under true triaxial monotonic and cyclic loading - Ming-Hui Cao; Sheng-Qi Yang; Wen-Ling Tian; Yan-Hua Huang; Yue Li (International Journal of Rock Mechanics and Mining Sciences, 2025)

Foodborne outbreak of enterotoxigenic Staphylococcus aureus at a school in Hebei, China - Xiaoyu Zheng; Shengnan Liang; Liang Wen; Hui Wang; Yuchao Bai; Yang Wang; Luyao Cao; Dingchen Li; Jinpeng Guo; Yong Chen; Changjun Wang; Xiong Liu; et al. (Food Research International, 2025)

Engineering ultrasmall red fluorescent carbon dots for targeted blood-brain barrier crossing, oxidative stress alleviation and mitochondrial repair in cerebral ischemia-reperfusion injury treatment - Jiacheng Xu; Xidong Wu; Xinyue Cao; Shuoxun Chen; Maohua Chen; Zhiwei Li; Hui Hu; Liang Chen; Lipeng Gao; Yu Chen; Jun Sun (Chemical Engineering Journal, 2025)

Intensification of precipitation extremes in the three river headwaters region under global warming - Yunkai Zhang; Juan Du; Kai Li; Chun Zhou; Zhen Liu; Biqiong Wu; Hui Cao; Li Zhou; Tianqi Ao (Theoretical and Applied Climatology, 2025)

Lotus japonicus CIP73 functions as a transcriptional repressor to inhibit Nodule Inception gene expression in nodule symbiosis - Hao Li; Yajuan Ou; Jidan Zhang; Aifang Xiao; Zhongming Zhang; Yangrong Cao; Hui Zhu (Plant and Soil, 2025)

Retraction Note to: miR-365b-3p adsorbed by HCG18 inhibits the proliferation and angiogenesis of stomach adenocarcinoma by downregulating STC1 - Hui Li; Jian Song; Rui Hou; Yingdong Cao; Huaili Xu (Molecular & Cellular Toxicology, 2025)

Abundant taxa enhanced stability of fungal communities according to reduced nitrogen fertilization - Heming Han; Bo Zhang; Hao Liu; Yue Li; Xu Weidong; Liting Zhang; Hui Cao; Feng Wang (Soil and Tillage Research, 2025)

Mechanism study of enhanced gas recovery and CO2 storage in naturally fractured carbonate reservoirs using a dual-permeability model coupled with association equation of state - Wei Xiong; Yu-Long Zhao; Lie-Hui Zhang; Shao-Mu Wen; Li-Li Liu; Zheng-Lin Cao; Cheng Cao; Xiang-Yu Liu; Xian-Yu Jiang (Gas Science and Engineering, 2025)

A new insight into the mechanism of cadmium-induced nephrotoxicity and antagonism of selenium nanoparticles: modulation of MTF1-MT axis dependent metal homeostasis - Yi-Xi Tang; Hui-Lin Cao; Jia-Rong Hou; Jian Chen; Shi-Yong Zhu; Yun-Shuang Liang; Zhou-Yi Yang; Kanwar Kumar Malhi; Xin-Yue Mao; Jin-Long Li (Environmental Pollution, 2025)

Crystallization and deposition of mixed potassium and sodium salts in supercritical water - Libo Lu; Zijian Fang; Shi Liu; Xujun Li; Wen Cao; Hui Jin; Yunan Chen; Liejin Guo (Desalination, 2025)

Senkyunolide I prevent chondrocytes from oxidative stress through Nrf2/HO-1 signaling pathway - Pengbin Li; Wenjuan Tang; Haiyan Wen; Siqi Zhou; Hui Cao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Properties and functions of acylated starch with short-chain fatty acids: a comprehensive review - Xin Li; Jingyi Gao; Wei Chen; Jiachen Liang; Wenjie Gao; David Mahoudjro Bodjrenou; Hongliang Zeng; Yi Zhang; Mohamed A. Farag; Hui Cao; Baodong Zheng (Critical Reviews in Food Science and Nutrition, 2025)

Study on the early warning index gases of lignocellulosic biomass during the auto-oxidation process - Jinhu Li; Mengru Cai; Qin Cao; Hui Zhuo; Wei Lu; Tenneh Maria Andrews (Process Safety and Environmental Protection, 2025)

Selection and validation of reference genes for quantitative real-time PCR analysis across tissues at different developmental stages in Taraxacum kok-saghyz - Yongmei Li; Yuan Yao; Tiancheng Xu; Xue Yang; Yuting He; Shengmin Zhang; Qingbiao Xie; Jie Cao; Chaorong Tang; Hui Liu (Journal of Plant Physiology, 2025)

Integrated metabolomics and transcriptomics analyses for understanding the mechanism underlying amantadine-induced toxicity in Laminaria japonica - Xiaohan Wang; Yao Lu; Xiaojie Li; Minglei Wang; Xiaojing Liu; Hui Huang; Wei Cao; Yongchun Liu; Lihua Ren; Yingjiang Xu (Journal of Hazardous Materials, 2025)

Effect and mechanism of calcium ions on the astringency in green tea infusion and epigallocatechin gallate solution: An in vitro oral soft tribology study - Long-Jie Xu; Qing-Qing Cao; Si-Han Deng; Wen-Jiang Dong; Qian Zou; Yong-Quan Xu; Xing-Hui Li (Food Chemistry, 2025)

Effect of adding Pickering emulsion containing oregano essential oil on the storage quality of Harbin red sausage - Lingyu Yin; Yuhang Cao; Meihui Wang; Yi Deng; Fei Li; Baohua Kong; Qian Liu; Hui Wang (Food Bioscience, 2025)

Computational design and efficacy assessment of Bufalin-Dendrimer nanoformulation for enhanced cancer therapy - Yurong Sun; Yinhua Lin; Huaitao Sun; Junfa Yang; Hui Cheng; Jia Yi; Wenqiang Li; Gen Lu; Cheng Zhao; Yuge Jiang; Xinyu Zhao; Qinglin Li; et al. (Chemical Engineering Journal, 2025)

Microfluidic-oriented assembly of MXene composite fibers for flexible zinc ion supercapacitors with high energy density - Fanyu Xie; Yuan Du; Menghan Chu; Xiaoyu Jia; Hui Cao; Rui Zhang; Hongwei Li; Mei Zhang (Chemical Engineering Journal, 2025)

Cucumber green mottle mosaic virus encodes additional small proteins with specific subcellular localizations and virulence function - Pan Gong; Mengxin Gao; Yalin Chen; Mingzhen Zhang; Yucong Huang; Xiaohua Hu; Siwen Zhao; Hui Zhang; Mengjiao Pan; Buwei Cao; Qingtang Shen; Yong Liu; et al. (Science China Life Sciences, 2025)

Nrf2 Ameliorates Sevoflurane-Induced Cognitive Deficits in Aged Mice by Inhibiting Neuroinflammation in the Hippocampus - Junhua Li; Jinfeng Li; Yafang Liu; Chuwen Hu; Hui Xu; Dong Cao; Rong Zhang; Kun Zhang (Molecular Neurobiology, 2025)

Angle-resolved magneto-chiral anisotropy in a non-centrosymmetric atomic layer superlattice - Long Cheng; Mingrui Bao; Xue Zhang; Jingxian Zhang; Qun Yang; Qiang Li; Hui Cao; Dawei Qiu; Hui Li; Guanglei Cheng; Hua Zhou; Jian-Min Zuo; et al. (Science Bulletin, 2025)

Decarbonization absorption of ship exhaust gas and solvent regeneration by a high-gravity method - Jianlu Zhu; Nan Li; Qi Nie; Hang Cao; Hui Han; Qihui Hu; Yuxing Li; Jiang Zhao; Chao Shang; Ming Zhang (Fuel, 2025)

The simulated in vitro infant gastrointestinal digestion of lipid droplets covered with milk fat globule membrane components: The role of interface layers - Zhixi Li; Yu Cao; Xiankang Fan; Hui Zhou; Pengjie Wang; Hao Zhang; Yi Wang; Ran Wang; Jie Luo (Food Research International, 2025)

Differentiation of Citri Reticulatae Pericarpium varieties via HPLC fingerprinting of polysaccharides combined with machine learning - Min-yong Zhong; Meng-ning Li; Wen-shu Zou; Si-qi Hu; Jiang-nan Luo; Qing-xiang Jiang; Qiu-fang Cao; Long-fei Lin; Zhi-xin Wang; Hui Li; Wen-wen Deng (Food Chemistry, 2025)

Low-frequency ultrasound-driven piezoelectric films repair neuro-immune circuits in diabetic wound healing - Chenyan Yu; Ying Hu; Xin Zhang; Kaixu Yu; Lang Chen; Wenqian Zhang; Shengming Zhang; Zhenhe Zhang; Ruiyin Zeng; Yuheng Liao; Yanzhi Zhao; Lin Gan; et al. (Chemical Engineering Journal, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Steering CO2 electroreduction to hydrocarbons over 2D thiol-based conductive metal-organic framework - Qiu-Jin Wu; Duan-Hui Si; Yu-Liang Dong; Qian Chen; Li-Li Han; Rong Cao; Yuan-Biao Huang (Science Bulletin, 2025)

Reapplication of glyphosate mitigate fitness costs for soil bacterial communities - Hao Liu; Cunzhi Zhang; Bo Zhang; Weidong Xu; Ruoling Zhang; Liting Zhang; Yue Li; Heming Han; Hui Cao (Journal of Environmental Management, 2025)

Construction of ultra-light and flexible aerogels with superior high oil sorption capacity by controlling the mechanical property of SiO2 nanofibers - Meng-Jie Chang; Ge Bai; Jun Liu; Xin Li; Hui Wang; Shu-Yi Hu; Qiu-Yu Hu; Shi-Shun Cao; Jie Yang (Journal of Environmental Chemical Engineering, 2025)

Magnetic graphene-enhanced exonuclease III assisted amplification strategy driven carbon nanozyme for tri-mode detection of Escherichia coli O157:H7 - Yuwei Ren; Lulu Cao; Zongyang Li; Xin Zhang; Hui Li; Rui Jiao; Xiaoyu Yu; Zhao Liang; Ganghui Li; Xiyang Xia; Na Ling; Danfeng Zhang; et al. (Food Chemistry, 2025)

The structures of two polysaccharides from Fructus Corni and their protective effect on insulin resistance - Guang-Yuan Ma; Lu-Kuan Hou; Jia-Hui Guo; Jing-Chun Sun; Qiuna Nong; Yu-Fan Wang; Sheng-Wei Hu; Wen-Jing Zhao; Jin Tan; Xiao-Feng Liu; Yuan Guo; Bo-Jing Zhang; et al. (Carbohydrate Polymers, 2025)

Decrease in urban-rural differences of nighttime humid heatwaves in the Yangtze River Delta, China - Wenqing Zhou; Liping Zhang; Qin Zhang; Yi Li; Gangsheng Wang; Zhenyu Tang; Xiao Li; Zhengfeng Bao; Hui Cao; Benjun Jia (Atmospheric Research, 2025)

Morphological characteristics and distribution of antennal sensilla of Spodoptera litura (Lepidoptera: Noctuidae) using scanning electron microscopy - Yong-Ping Li; Hai-Yan Zhou; Hui Ye; Robert A. Haack; Yuan Yang; Qiu-Lian Hu; Ming-Min Jiang; Jun Cao (Zoomorphology, 2025)

The Secondary Metabolites of Bacillus subtilis Strain Z15 Induce Apoptosis in Hepatocellular Carcinoma Cells - Reyihanguli Aimaier; Haoran Li; Wenzhi Cao; Xiyuan Cao; Hui Zhang; Jia You; Jingjing Zhao; Qi Zhang; Li Yin; Qinshuang Mei; Xiaorong Zhang; Weiquan Wang; et al. (Probiotics and Antimicrobial Proteins, 2025)

Curcumol attenuates hyperproliferation and inflammatory response in a psoriatic HaCaT keratinocyte model by inhibiting the PI3K-Akt pathway and ameliorates skin lesions and inflammatory status in psoriasis-like mice - Mutian Niu; Xiaolong Li; Mingzhao Li; Fangru Chen; Hui Cao; Qingbo Liu; Bin Liang; Guangyu Pan; Chengqin Liang; Jintao Gao (Inflammopharmacology, 2025)

A Rare Patient of SEZ6L2 Antibody–Associated Cerebellar Ataxia - Chen-hui Cao; Wen-li Li; Yao Zhang; Ting Wei; Chun-lin Yang; Xiao-li Li; Bin Liu (The Cerebellum, 2025)

Co-combustion characteristics of coal gasification fly ash and coal gangue preheated by circulating fluidized bed - Jicheng Hui; Jiangong Lin; Shujun Zhu; Zhaoyang Li; Xiaoyu Zhang; Xiaoyang Cao; Jianguo Zhu; Qinggang Lyu (Waste Management, 2025)

Human-perceived temperature changes linked to local climate zones under extreme hot and cold weathers: A study in the North China Plain - Xiang Li; Ming Luo; Jianfeng Li; Sijia Wu; Hui Zhang; Ziwei Huang; Qiuting Wang; Wenyue Cao; Yu Tang; Xiaoyu Wang (Sustainable Cities and Society, 2025)

Characterization of emulsion co-encapsulated with probiotics and quercetin and its effect on the storage quality of Harbin red sausage - Yuhang Cao; Lingyu Yin; Fei Li; Yi Deng; Baohua Kong; Qian Liu; Hao Wang; Hui Wang (Meat Science, 2025)

How bedding-parallel fractures affect fluid activity in a relatively closed lacustrine shales system: Evidence from calcite veins - Zilong Li; Kelai Xi; Xiaobing Niu; Xiujuan Wang; Wenzhong Ma; Xiao Hui; Jiangyan Liu; Changyu Fan; Miruo Lin; Keyu Liu; Yingchang Cao (Marine and Petroleum Geology, 2025)

Construction of NCQDs/Ag3PO4/Ag composite with dual-channel charge transfer property for efficient photocatalytic degradation of ciprofloxacin - Yu Yao; Chengqi Lu; Qianhong Shen; Yijin Yang; Kaiyue Huang; Libei Jiang; Jie Liu; Yue Li; Xudan Cao; Hui Yang (Journal of Water Process Engineering, 2025)

A new method for quantitative characterization of dynamic migration behavior of NaCl in beef during marinating - Yingjie Feng; Fujia Dong; Cheng Wu; Jiarui Cui; Guangxian Wang; Zhongxiong Zhang; Songmin Cao; Sijia Liu; Hui Li; Yingkun Shi; Jianguo Yu; Songlei Wang (Food Research International, 2025)

MYR ameliorated MSG-induced immune dysfunction in HFD mice via modulation of gut microbiota and SCFAs metabolism - Qiaoling Su; Li Yang; Jianbo Xiao; Hui Cao; Hui Wang (Food Bioscience, 2025)

Semi-artificial bacterial pyroptosiser for reverse the metabolic reprogramming of tumor microenvironment - Guoqing Feng; Deping Wang; Bowen Li; Shuchao Wang; Yingjian Hao; Xin Zhou; Niansong Qian; Qing-hui Meng; Jimin Cao; Bin Zheng; Xianhui Ruan (Chemical Engineering Journal, 2025)

Macrophage-targeted, ROS-removing and H2S-releasing nanomicelle encapsulated in hydrogel microspheres for the treatment of osteoarthritis - Jun Tao; Hui Deng; Zhengnan Li; Liping Cao; Yanfei Rao; Zhanhai Yin (Chemical Engineering Journal, 2025)

Breaking the photoelectrochemical activity-battery voltage trade-off for efficient photocharging of TEMPO/quinone redox flow battery - Weicheng Zhou; Mingyao Liu; Yuexian Cao; Youming Sun; Qingbo Chang; Xuefei Zhao; Hui Wang; Shengzhong Liu; Jingying Shi; Can Li (Chemical Engineering Journal, 2025)

Peficitinib suppresses diffuse-type tenosynovial giant cell tumor by targeting TYK2 and JAK/STAT signaling - Shan Lu; Chenxi Cao; Wenjia Zhang; Jiayi Li; Jingli Yang; Zisheng Huang; Zhijun Wu; Baitao Liu; Hongjie Huang; Haijun Wang; Yongjian Wang; Dingge Liu; et al. (Science China Life Sciences, 2025)

Cadmium induces spontaneous abortion by impairing endometrial stromal cell decidualization - Xue-Ke Zhang; Xuan Li; Xing-Xing Han; Dong-Ying Sun; Yu-Qin Wang; Zi-Zhuo Cao; Lu Liu; Zi-Han Meng; Guo-Jing Li; Yu-Jie Dong; Dan-Yang Li; Xiao-Qing Peng; et al. (Toxicology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Longitudinal landscape of immune reconstitution after acute SARS-CoV-2 infection at single-cell resolution - Lili Ren; Yiwei Liu; Yeming Wang; Chao Wu; Li Guo; Lan Chen; Xinming Wang; Yan Xiao; Lixue Huang; Jingchuan Zhong; Jiacheng Yao; Lu Liu; et al. (Science Bulletin, 2025)

Preparation and characterization of pickering emulsions stabilized by zein/quercetin/quaternary ammonium chitosan composite nanoparticles with antibacterial effect - Lingyu Yin; Yuhang Cao; Yi Deng; Fei Li; Baohua Kong; Qian Liu; Hui Wang (Journal of Food Engineering, 2025)

Regional and longitudinal dynamics of human milk protein components assessed by proteome analysis on a fast and robust micro-flow LC–MS/MS system - Junxia Cao; Xinling Cui; Hai Lu; Hui Wang; Wen Ma; Zhan Yue; Kemiao Zhen; Qiaosi Wei; Hongmei Li; Shilong Jiang; Wantao Ying (Food Chemistry, 2025)

A cost-effective, salt-resistant and environmentally stable solar evaporator with a wetting-gradient bilayer structure for long-term seawater desalination - Haoze Du; Yiwei Li; Jing Meng; Renjie Wei; Qingying Meng; Yuhao Cao; Ning Cui; Hongji Liu; Hui Yang (Chemical Engineering Journal, 2025)

The unity/diversity framework of executive functions: behavioral and neural evidence in older adults - Sheng-Ju Guo; Ping Wang; Li-Zhi Cao; Hui-Jie Li (GeroScience, 2025)

Biological analysis of phage vB_AhaP_PT2 and treatment rescued crucian carp infected with Aeromonas hydrophila - Shuang Liang; Ruiqi Liang; Sayed Haidar Abbas Raza; Qixing Huang; Tingxuan Li; Huifang Bai; Chao Feng; Liang Xin; Hui Guo; Shun Wang; Jiahao Yu; Yuan Cao; et al. (Aquaculture, 2025)

Top-to-south shear at the base of the eastern Tethyan Himalayan Sequence during the Eocene-Oligocene Himalayan orogeny - Zhiqin Xu; An Yin; Hua Xiang; Qin Wang; Guangwei Li; Hanwen Dong; Hui Cao; Jianguo Gao (Tectonophysics, 2025)

Evidence of sewage discharge on the coalescence mechanism of aquatic microbial communities during high amplitude hydrological periods - Xin Kou; Shier Huang; Rui Bian; Qingwen Tang; Hui Wang; Song Liu; Li Wang; Weixiao Qi; Xiaofeng Cao; Huachun Lan; Huijuan Liu; Jiuhui Qu (Science of The Total Environment, 2025)

Mechanism of preheating modification on NO emission reduction during peak shaving of different coal ranks - Jicheng Hui; Shujun Zhu; Zhaoyang Li; Xiaoyang Cao; Qinggang Lyu (Process Safety and Environmental Protection, 2025)

Turning waste into wealth: Bifunctional electrospun membrane based on waste expanded polystyrene for oil–water separation and anti-counterfeiting - Yuanquan Wu; Jiaqi Hui; Shuohang Gao; Yunjie Fan; Pengfei Li; Zheng Yan; Dan Liu; Kemei Pei; Xuebo Cao (Chemical Engineering Journal, 2025)

In situ construction of ion/electron conductive components via lithiation strategy enhancing cycling capability and initial Coulombic efficiency of Si anode - Jingfeng Cao; Xiang Yan; Dan Li; Liuyi Hu; Tiansheng Chen; Weiwei Gao; Wenlong Song; Xinhui Xia; Yang Xia; Wenkui Zhang; Hui Huang (Chemical Engineering Journal, 2025)

Overexpression of PtNRPS1 enhances diatom-mediated bioremediation of salicylate pollution - Dong-Sheng Zhao; Yu-Ting Chen; Jia-Min Xu; Xiao-Li Liu; Yi-Cheng Xu; Peng Cao; Junliang Li; Shengqin Wang; Nan Li; Yong Li; Shu-Ming Li; Xiufeng Yan; et al. (Bioresource Technology, 2025)

Factors affecting the different growth rates of PM2.5：Evidence from composition variation, formation mechanisms, and importance analysis of water-soluble inorganic ions with case study in northern China - Huan Li; Ting Zhang; Hui Su; Sui Xin Liu; Ying Qiang Shi; Lu Yao Wang; Dong Dong Xu; Jia Mao Zhou; Zhu Zi Zhao; Qi Yuan Wang; Steven Sai Hang Ho; Yao Qu; et al. (Atmospheric Environment, 2025)

The complete genome sequence of proteases-producing Shewanella sp. H8 isolated from Antarctica - Xiao-Hui Yang; Jia-Yi Song; Kang Li; Mei-ling Sun; Hai-Yan Cao; Peng Wang; Yi Zhang (Marine Genomics, 2024)

Disclosing the key role of Fe/As/Cu in community co-occurrence and microbial recruitment in metallurgical ruins - Shuai Gao; Shuzhen Li; Shuangfeng Cao; Hui Zhong; Zhiguo He (Journal of Hazardous Materials, 2024)

Anthropogenic forcing decreases the probability of the 2020 Yangtze River extreme flood and future risk - Xiao Li; Liping Zhang; Gangsheng Wang; Hui Cao; Hairong Zhang; Benjun Jia; Zhiling Zhou; Lina Liu; Lu Zhang (Atmospheric Research, 2024)

Fine mapping of QGPC.caas-7AL for grain protein content in bread wheat - Dehui Zhao; Jianqi Zeng; Hui Jin; Dan Liu; Li Yang; Xianchun Xia; Yubing Tian; Yan Zhang; Shuanghe Cao; Wei Zhu; Chunping Wang; Zhonghu He; et al. (Theoretical and Applied Genetics, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Morpho-histological and Transcriptome Analysis Reveal the Unreduced Sperm Formation Mechanism in cdk1-Depletion Zebrafish - Yunbang Zhang; Rongyun Li; Hui Li; Yuwei Huang; Yihui Mei; Yuxuan Zheng; Yankun Guo; Zihao Zhou; Zhonglin Yong; Ying Zhao; Wenjing Dong; Jian Gao; et al. (Marine Biotechnology, 2024)

Deciphering heart failure: an integrated proteomic and transcriptomic approach with experimental validation - Jun Cao; Zhaohai Su; Bilong Zhang; Jiangyong Yang; Yueting Wang; Ling Huang; Gang Cao; Hui Xie; Xiutong Zhong; Hengqing Zhu; Rengui Jiang; Tian Li; et al. (Functional & Integrative Genomics, 2024)

Jeotgalibacillus haloalkalitolerans sp. nov., a novel alkalitolerant and halotolerant bacterium, isolated from the confluence of the Fenhe River and the Yellow River - Ya-Fei Zhang; Yun-Lin Peng; Yong-Hui Xiao; Bing Yu; Ming-Yue Cao; Zhi-Ling Zhang; Le-Qun Huang; Yi Li (Antonie van Leeuwenhoek, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Evaluation coupling-coordination relationship between car anthropogenic heat release and local temperature at multi-spatiotemporal scales - Zheng Cao; Junying Li; Wang Jin; Weiqi Zhou; Yong Xu; Zhifeng Wu; Fangyuan Yu; Hui Sun (Urban Climate, 2024)

Serum arsenic augments gallstone risk in Henan rural cohort with multiple metal exposure - Qian Zhang; Yating Li; Han Hu; Meichen Tian; Tingting Cao; Hui Wu; Weidong Wu; Guofu Zhang (Science of The Total Environment, 2024)

Impacts of urban expansion on air temperature and humidity during 2022 mega-heatwave over the Yangtze River Delta, China - Wenqing Zhou; Liping Zhang; Gangsheng Wang; Qin Zhang; Hui Cao; Hairong Zhang; Benjun Jia; Zhenyu Tang; Xiao Li; Lina Liu (Science of The Total Environment, 2024)

Identification and bioactivity evaluation of twelve previously undescribed depsidone derivatives from Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Xiao-Fan Liu; Jin-Yuan Yang; Fan-Zhu Meng; Hao Cao; Da-Hong Li; Hui-Ming Hua (Phytochemistry, 2024)

Sulfamethoxazole degradation in tri-electrode microbial electrochemical systems: Metabolomic and Metagenomic insights into organic pollution effects - Chong Zhang; Jijing Hu; Hui Wang; Helai Cheng; Xian Cao; Takashi Sakamaki; Xianning Li (Journal of Environmental Management, 2024)

Blood mercury mediates the associations between fish consumption and serum uric acid levels among Chinese adults: A nationally representative study - Changzi Wu; Bing Wu; Yingli Qu; Hui Fu; Yue Chen; Yifu Lu; Saisai Ji; Liang Ding; Zheng Li; Qi Sun; Miao Zhang; Xu Zhang; et al. (Environmental Research, 2024)

Polymerized lignin based carbon nanofiber for high-performance energy generator and storage - Chuangqi Zheng; Qiping Cao; Lei Pu; Jingyu Xu; Hui Gong; Ziyi Shen; Kaibin Chu; Dechao Chen; Qin Li; Ning Han; Yao Li (Chemical Engineering Journal, 2024)

A WUSCHEL-related homeobox transcription factor, SlWOX4, negatively regulates drought tolerance in tomato - Hui Li; Wanying Ma; Xiao Wang; Hongling Hu; Lina Cao; Hui Ma; Jingwei Lin; Ming Zhong (Plant Cell Reports, 2024)

Exploring the short-term effects of extreme temperatures on tuberculosis incidence in Shantou, China: a Coastal City perspective - Yaqian Su; Ruiming Chen; Zhuanghao Chen; Jianxiong Lin; Hui Fu; Zicheng Cao; Qiaocheng Chang; Liping Li; Suyang Liu (International Archives of Occupational and Environmental Health, 2024)

Oxaliplatin lipidated prodrug synergistically enhances the anti-colorectal cancer effect of IL12 mRNA - Hui Liu; Yating Du; Desheng Zhan; Wenjun Yu; Yan Li; Aiping Wang; Jianpeng Yin; Haiqiang Cao; Yuanlei Fu (Drug Delivery and Translational Research, 2024)

The first dimeric indole-diterpenoids from a marine-derived Penicillium sp. fungus and their potential for anti-obesity drugs - Hui-Fang Du; Lei Li; Ya-Hui Zhang; Xu Wang; Cheng-Yan Zhou; Hua-Jie Zhu; Charles U. Pittman; Jia-Wen Shou; Fei Cao (Marine Life Science & Technology, 2024)
Obesity has become a worldwide health problem. Seeking natural products with anti-obesity activity from lots of fungi has drawn the attention of pharmacologists. In our study, dipenipenoids A and B ( 1 and 2 ), the first dimeric indole-diterpenoids with a rare C-20–C-22′ linkage, and their monomers ( 3 and 4 ), were isolated from a marine-derived Penicillium sp. CF-06 fungus from Suaeda salsa . The absolute configurations of 1 – 3 were assigned by the calculated TDDFT ECD method. The structure of 4 was verified by a single-crystal X-ray diffraction method for the first time. Interestingly, 1 and 2 displayed significant effects on the differentiation of 3T3-L1 adipocytes by down-regulating the expression of peroxisome proliferator-activated receptor gamma (PPAR γ ) and CCAAT/enhancer binding protein alpha (C/EBP α ) proteins, while monomers 3 and 4 exhibited no activity. Molecular docking results explained the mechanism that the interaction between dimer 1 and PPAR γ was stronger than that between monomer 3 and PPAR γ . Our research could provide new insight for the discovery of anti-obesity drugs.

Nutrient regeneration patterns for initiating and maintaining algae blooms-a case study of in Lake Taihu - Hui Li; Yingying Cai; Huatang Deng; Zhenhua Qin; Jianfen Li; Xiuyun Cao; Yiyong Zhou; Chunlei Song; XinBin Duan (Chemosphere, 2024)

Freshwater microconchids from the Tanzhuang Formation (Middle-Late Triassic) in North China - Hao Yang; Yue Su; Hui-Jun Chen; Yi-Ran Cao; Meng-Yang Zhang; Rui Li; Dao-Liang Chu (Palaeoworld, 2024)

Improving the storage quality of Harbin red sausages by quaternized chitosan/sodium alginate coating curcumin nano-emulsion - Ying-ao Zhu; Fei Li; Meihui Wang; Yuhang Cao; Baohua Kong; Qian Liu; Hui Wang; Qian Chen (Meat Science, 2024)

Associations of prenatal exposure to individual and mixed organophosphate esters with ADHD symptom trajectories in preschool children: The modifying effects of maternal Vitamin D - Han Li; Juan Tong; Xing Wang; Mengjuan Lu; Fengyu Yang; Hui Gao; Hong Gan; Shuangqin Yan; Guopeng Gao; Kun Huang; Yunxia Cao; Fangbiao Tao (Journal of Hazardous Materials, 2024)

Experimental study on peak shaving during preheating combustion for different coal ranks: Thermal modification and variable load operation - Jicheng Hui; Shujun Zhu; Zhaoyang Li; Jiangong Lin; Xiaoyang Cao; Qinggang Lyu (Fuel, 2024)

Portulaca oleracea L. polysaccharide ameliorates ulcerative colitis by regulating the immune system and gut microbiota - Yang Yang; Xiechen Zhou; Guiyan Jia; Hui Zhao; Yan Li; Junyang Cao; Zijian Guan; Rui Zhao (Food Bioscience, 2024)

Cu-EDTA decomplexation by UV/peracetic acid oxidation and coupled Cu recovery by alkaline precipitation: Efficiency and mechanism - Leliang Wu; Dunyu Sun; Hui Cao; Chengdu Qi; Longjiong Chen; Huijuan Zhang; Dequan Zhang; Yao Li; Zhuorong Huang; Guilong Peng; Huan He; Shaogui Yang (Chemical Engineering Journal, 2024)

Tailor-made the ultrathin nanosheet and acid site accessibility of mordenite zeolite for carbonylation of dimethyl ether - Feng Chen; Xiao-Bo Feng; Pan Deng; Li-Yun Zhang; Jing-Ping Zhao; Yu-Hui Wang; Bo-Yu Tao; Xiao-Yan Zhao; Jing-Pei Cao; Hong-Cun Bai (Chemical Engineering Journal, 2024)

Maximize coordinately unsaturated metal sites via removal of compact MOF external surface: Enhanced Fenton-like performance inside yolk@shell nanoreactor - Wanting Hui; Zixin Li; Shouchun Ma; HongYan Liu; Yanqiu Zhang; Wenqi Ding; Yaodan Cao; Tongjie Yao; Jie Wu (Chemical Engineering Journal, 2024)

A general climatology of categorized Martian ionospheric irregularities - Xin Wan; Jiahao Zhong; Yongqiang Hao; Chao Xiong; Hui Wang; Yutian Cao; Jun Cui; Yiwen Liu; Qiaoling Li; Jiawei Kuai (Science China Earth Sciences, 2024)

RETRACTED ARTICLE: miR-365b-3p adsorbed by HCG18 inhibits the proliferation and angiogenesis of stomach adenocarcinoma by downregulating STC1 - Hui Li; Jian Song; Rui Hou; Yingdong Cao; Huaili Xu (Molecular & Cellular Toxicology, 2024)

Cellulose-based yellow-green emitting carbon dots with large Stokes shift as effective “turn off-on” fluorescence platforms for Cr (VI) and AA dual efficacy detection - Yan-feng Li; Xian Zhang; Qian Lu; Jing-zhen Cao; Sheng Gao; Qin-ze Liu; Xiao-xia Cai; Hui Zhao (Analytica Chimica Acta, 2024)

Prevalence of antibiotic resistance genes, heavy metal, and bacterial community composition in sea sediments influenced by Eriocheir sinensis breeding aquaculture - Hui Fu; Wei Sun; Yawei Cao; Qing Li; Xiaotong Wang; Zijie Zhou; Qian Meng; Tingyi Luo; Wei Gu; Qingguo Meng (Environmental Science and Pollution Research, 2024)

Novel Br-doped Bi2WO6 photocatalyst for high-efficiency removal of norfloxacin: mechanism and photocatalytic activity - Zhi Li; XiaoMei Zhu; ZhuoLing Chen; Na Cao; Hui Liu; Bing Sun (Environmental Science and Pollution Research, 2024)

The composition of the zebrafish intestinal microbial community varies under Bdellivibrio treatment from larvae to juveniles and adults - Haolin Mo; Qing Li; Qingsheng Cao; Haiyong Zhao; Lixin Wang; Hui Yang (Aquaculture, 2024)

Does supply match demand? Assessing the relationship between urban parks and residents from the perspective of equity and efficiency - Hui Cao; Pingxing Li; Weixuan Song; Jianglong Chen; Cheng Chen (Urban Forestry & Urban Greening, 2024)

Degradation of pyrene at high concentrations in sediment and the implications for the microbiome in microbial electrochemical systems - Chong Zhang; Xiaoyi Jiang; Shuai Zhang; Xian Cao; Hui Wang; Takashi Sakamaki; Xianning Li (Chemical Engineering Journal, 2024)

Co-Zn single atoms anchored carbon nanotubes derived from anti-perovskite carbides for boosted hydrogen evolution and oxygen reduction reactions - Liangliang Feng; Mengfei Zhou; Danyang He; Hongyan Yin; Yixuan Huang; Liyun Cao; Yuan Fang; Dewei Chu; Yipu Liu; Hui Chen; Guodong Li; Jianfeng Huang (Chemical Engineering Journal, 2024)

Copper phosphate-rotenone nanocomposites for tumor therapy through autophagy blockage-enhanced triphosadenine supply interruption and lipid peroxidation accumulation - Yi Ouyang; Ying Li; Chunmei Chen; Sheng Zhao; Mengyuan Wu; Benqing Zhou; Yang Cao; Hui Liu (Chemical Engineering Journal, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

TBC1D1 is an energy-responsive polarization regulator of macrophages via governing ROS production in obesity - Qi Wang; Ping Rong; Wen Zhang; Xinyu Yang; Liang Chen; Ye Cao; Minjun Liu; Weikuan Feng; Qian Ouyang; Qiaoli Chen; Hailong Li; Hui Liang; et al. (Science China Life Sciences, 2024)

Transcriptional kinetics of NADC34-like porcine reproductive and respiratory syndrome virus during cellular infection - Riteng Zhang; Hui Li; Honglin Xie; Peixin Wang; Chenfei Yu; Junda Li; Zengqi Yang; Basit Zeshan; Aiqiao Cao; Xinglong Wang (Archives of Virology, 2024)

Warming alters the network of physiological traits and their contribution to plant abundance - Guixiang Yuan; Eti E. Levi; Thomas A. Davidson; Torben L. Lauridsen; Martin Søndergaard; Zhenzhi Yang; Aiping Wu; Te Cao; Youzhi Li; Hui Fu; Erik Jeppesen (Science of The Total Environment, 2024)

Late Pliocene Bauhinia s.l. (Cercidoideae, Fabaceae) fossils from Tengchong, Yunnan, southwestern China - Rui Cao; Zhi-hui Song; Zhuo-er Wang; Zhao-shuai Wang; Han-shi Li; Jing-Yu Wu; Su-Ting Ding (Review of Palaeobotany and Palynology, 2024)

Material modification of electrodes in microbial electrochemical system to enhance electrons utilization on the electrode and its impact on microorganisms - Chong Zhang; Ke Yang; Yali Yuan; Xian Cao; Hui Wang; Takashi Sakamaki; Xianning Li (Journal of Hazardous Materials, 2024)

Preparation and modification of polymer microspheres, application in wastewater treatment: A review - Li-Hui Chen; Cao Ban; Mohamed H. Helal; Salah M. El-Bahy; M. Zeinhom; Shuang Song; Yong-Gang Zhao; Yin Lu (Journal of Environmental Management, 2024)

New insights into black carbon light absorption enhancement: A comprehensive analysis of two differential behaviors - Ruonan Fan; Yingying Ma; Wenxiang Cao; Shikuan Jin; Boming Liu; Weiyan Wang; Hui Li; Wei Gong (Environmental Pollution, 2024)

Energy strategy alteration, rather than toxicity itself, interferes with the population fluctuation of Brachionus plicatilis exposed to water-accommodated fractions (WAFs) of crude oil - Yuanyuan Li; Yaya Zhang; Hui Zhang; Mengxue Xu; Qiyue Cao; You Wang (Aquatic Toxicology, 2024)

Competitive relationships due to similar nutrient preferences reshape soil bacterial metacommunities - Heming Han; Hao Liu; Bo Zhang; Yue Li; Chuanhai Li; Hui Cao (Science of The Total Environment, 2024)

Return to the Moon: New perspectives on lunar exploration - Yangting Lin; Wei Yang; Hui Zhang; Hejiu Hui; Sen Hu; Long Xiao; Jianzhong Liu; Zhiyong Xiao; Zongyu Yue; Jinhai Zhang; Yang Liu; Jing Yang; et al. (Science Bulletin, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

Dynamic modulation of nodulation factor receptor levels by phosphorylation-mediated functional switch of a RING-type E3 ligase during legume nodulation - Hao Li; Yajuan Ou; Jidan Zhang; Kui Huang; Ping Wu; Xiaoli Guo; Hui Zhu; Yangrong Cao (Molecular Plant, 2024)

Elucidating GO/iron series mediated stable flora and electron transfer under different COD/SO42− ratios - Ke Li; Qiliang Cao; Hui Zhang; Yuqi Jin; Qiaochu Liang; Huixia Lan; Wudi Zhang; Yang Zhang (Journal of Water Process Engineering, 2024)

Novel polyurethane-degrading cutinase BaCut1 from Blastobotrys sp. G-9 with potential role in plastic bio-recycling - Zhitong Jiang; Xue Chen; Huizhen Xue; Zhoukun Li; Jinhui Lei; Muming Yu; Xin Yan; Hui Cao; Jie Zhou; Jiawei Liu; Mingna Zheng; Weiliang Dong; et al. (Journal of Hazardous Materials, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Copper ferrite nanoparticles anchored laser-induced graphene as novel nanoenzyme for the electrochemical catalyzing and sensing of β-estradiol in serum - Minghui Cai; Haixu Yao; Mengnan Li; Yan Yan; Yang Cao; Jiaxin Li; Huiyu Su; Wenwen Zhang; Hui Zhu; Feiyun Cui (Chemical Engineering Journal, 2024)

Curcumin-loaded biomimetic nanosponges for osteoarthritis alleviation by synergistically suppressing inflammation and ferroptosis - Huihui Xu; Su Liu; Yihao Wei; Siyang Cao; Jiapeng Deng; Guoqing Li; Weibei Sheng; Tiantian Qi; Peng Zhang; Jianjing Lin; Jian Weng; Fei Yu; et al. (Chemical Engineering Journal, 2024)

The promotion of the polycyclic aromatic hydrocarbons degradation mechanism by humic acid as electron mediator in a sediment microbial electrochemical system - Xian Cao; Xinyu Li; Hui Wang; Shuai Zhang; Haochi Zhang; Takashi Sakamaki; Xianning Li (Bioresource Technology, 2024)

Dependence of evolution of Cyanobacteria superiority on temperature and nutrient use efficiency in a meso-eutrophic plateau lake - Jing Cao; Yue Wu; Ze-kun Li; Ze-ying Hou; Tian-hao Wu; Zhao-sheng Chu; Bing-hui Zheng; Ping-ping Yang; Yi-yan Yang; Cun-sheng Li; Qian-hua Li; Xia Guo (Science of The Total Environment, 2024)

Genomic analysis of Cobetia sp. D5 reveals its role in marine sulfur cycling - Xiao-Mei Geng; Shi-Ning Cai; Hai-Xia Zhu; Zhi-Gang Tang; Chun-Yang Li; Hui-Hui Fu; Yi Zhang; Hai-Yan Cao; Peng Wang; Mei-Ling Sun (Marine Genomics, 2024)

Catalytic diesel soot combustion over FeCo2O4 monolithic catalysts with different morphologies - Zhenhai Fan; Hua Yang; Feiyang Qin; Jieyu Xiao; Hui Xian; Xingchuan Yang; Yi Yu; Guoji Liu; Li Xu; Chunmei Cao (Journal of Environmental Chemical Engineering, 2024)

A freestanding rotating triboelectric nanogenerator with large area and high efficiency for triboelectric plasma CO2 reduction - Hongjie Cao; Qinglong Ru; Dongyang Fang; Sumin Li; Nannan Liu; Wei Jiang; Hui Hu; Yongcui Yang; Guangqin Gu; Bao Zhang; Gang Cheng; Sanjun Yang; et al. (Chemical Engineering Journal, 2024)

Culture of cerebrospinal fluid-contacting neurons from neonatal mouse spinal cord - Liang Cao; Hui-Qian Zhang; Yu-Qi He; Ping-Jiang An; Lei-Luo Yang; Wei Tan; Gang Liu; Chun-Qing Wang; Xiao-Wei Dou; Qing Li (Cell and Tissue Banking, 2024)

A novel strategy for enhancing the stability of aptamer conformations in heavy metal ion detection - Shi Quan Qian; Min Yuan; Xian Wei Zuo; Hui Cao; Jin Song Yu; Li-Ling Hao; Kun Lin Yang; Fei Xu (Analytica Chimica Acta, 2024)

Alleviating effect of Astragalus polysaccharide on salinity-alkali stress-induced intestinal injury in hybrid crucian carp - Xin-yu Lei; Jia Sun; Cheng-cheng Bi; Xin Wang; Xue Cao; Hui-qing Wang; Yue-hong Li (Aquaculture International, 2024)

Comparison of acidity and chemical composition of summertime cloud water and aerosol at an alpine site in Northwest China: Implications for the neutral property of clouds in the free troposphere - Minxia Shen; Jianjun Li; Yali Liu; Wenting Dai; Gehui Wang; Weining Qi; Yukun Chen; Xiao Guo; Yifan Zhang; Lu Li; Yue Cao; Qiao Feng; et al. (Science of The Total Environment, 2024)

Rice straw returning enhances cadmium activation by accelerating iron cycling thus hydroxyl radical production in paddy soils during drainage - Hui Huang; Zhuoqi Tian; Di Guo; Zhixian Tang; Ronghua Li; Amjad Ali; Zhengxian Cao; Haiying Lu; Yu Shen; Yongli Zhu; Jiangang Han (Science of The Total Environment, 2024)

Sublethal effect and detoxifying metabolism of metaflumizone and indoxacarb on the fall armyworm, Spodoptera frugiperda - Li Zhang; Hui-Zi Wu; Pei-Yun He; Hai-Qun Cao; Wan-Na Zhang; Ying-Chuan Peng; Cheng-Wang Sheng (Pesticide Biochemistry and Physiology, 2024)

Numerical simulation analysis of stable flow of hydrate slurry in gas-liquid-solid multiphase flow - Xiao-Fang Lv; Kai-Yue Xu; Yang Liu; Chuan-Shuo Wang; Ming-Guo Peng; Hui Du; Shuang-Cindy Cao; Qian-Li Ma; Shi-dong Zhou; Shang-Fei Song (Ocean Engineering, 2024)

Extracellular electron transfer-coupled heavy metal reduction in biogeobattery: Perspectives and challenges - Hui Wang; Xizi Long; Waheed Miran; Yaqian Zhao; Xian Cao; Xianning Li; Xin Wang; Fei Yang (Journal of Cleaner Production, 2024)

An oxygen isotope perspective on the break-up of the Rodinia supercontinent - Hao Zou; Chang-Cheng Huang; Hua-Wen Cao; Chun-Mei Liu; Hui-Dong Yu; Franco Pirajno; Xian-Hua Li (Earth-Science Reviews, 2024)

Enhanced tandem hydrogenation of nitroaromatics to alicyclic amines via Pt-Ru synergistic catalysis - Jiale Wu; Jiajun Zhang; Liguo Wang; Ziqiang Han; Xiang Hui; Yan Cao; Jianhui Shi; Shuang Xu; Peng He; Huiquan Li (Chemical Engineering Journal, 2024)

Dimethylamine-tuned guanidinium arylphosphonate iHOFs and superprotonic conduction Nafion hybrid membranes for DMFCs - Xiang-Tian Bai; Li-Hui Cao; Xu-Yong Chen; Shu-Hui Li; Jia-Hao Zhang (Chemical Engineering Journal, 2024)

Characteristics of transfer zones under the influence of pre-existing faults and regional stress transformation: Wenchang A subsag, Zhujiang River Mouth Basin, northern South China Sea - Wei Li; Mingyue Cao; Meifang Meng; Caiwei Fan; Hui Li; Jia Li; Wanqiu Wu; Ruiqing Qin; Xingan Li; Yiming Liu (Journal of Oceanology and Limnology, 2024)

The promotion of the atrazine degradation mechanism by humic acid in a soil microbial electrochemical system - Xinyu Li; Xian Cao; Hui Wang; Yilun Sun; Shuai Zhang; Sirapat Khodseewong; Takashi Sakamaki (Journal of Environmental Management, 2024)

A novel derivative synchronous fluorescence method for the rapid, non-destructive and intuitive differentiation of denitrifying bacteria - Huang-Zhou Lv; Jinliang Chen; Yan Zhao; Yu Li; Shuo-Hui Cao; Wei-Peng Cai; Liang Shen; Yinghua Lu; Yao-Qun Li (Journal of Environmental Management, 2024)

High contributions of fossil fuel sources to char-EC/soot-EC at a high-altitude site: Direct radiative effects and transport pathway - Huikun Liu; Qiyuan Wang; Yao Qu; Jie Tian; Li Li; Nan Ma; Yaqing Zhou; WeiKang Ran; Hui Su; Yongming Han; Giulia Pavese; Junji Cao (Fuel, 2024)

Synchronous fluorescence spectra-based machine learning algorithm with quick and easy accessibility for simultaneous quantification of polycyclic aromatic hydrocarbons in edible oils - Jia-Wen Wei; Jia-Rong He; Shi-Yi Chen; Yi-Han Guo; Xuan-Zhu Huo; Nuan Zheng; Shuo-Hui Cao; Yao-Qun Li (Food Control, 2024)

The effects of sowing date on maize: Phenology, morphology, and yield formation in a hot subtropical monsoon region - Zhong-Yang Cao; Zhi-Hui Chen; Bin Tang; Qiang Zeng; Huan-Le Guo; Wan-Hua Huang; Yu Luo; Si Shen; Shun-Li Zhou (Field Crops Research, 2024)

Inhibiting phase conversion and improving cyclic stability of Ni-rich layered oxide by high-valence element concentration gradient doping - Ruijuan Wang; Jiarui Chen; Yixu Zhang; Zhi Li; Shuang Cao; Xiaolin Liu; Hui Hu; Lei Wu; Yongqiang Shen; Xianyou Wang (Chemical Engineering Journal, 2024)

Enhanced electro-optical properties of polymer-dispersed liquid crystals co-doped with fluorescent molecules and nanoparticles for multifunctional applications - Yinfu Lu; Dongliang Yang; Hong Gao; Xin Du; Yuzhen Zhao; Dong Wang; Zemin He; Zongcheng Miao; Hui Cao; Zhou Yang; Wanli He; Yuzhan Li (Chemical Engineering Journal, 2024)

RuBisCO activase alleviates adverse effects of Nilaparvata lugens feeding on photosynthesis in Oryza sativa - Qingliang Li; Xia Sun; Wei Tan; Yan Liang; Hui Cao; Deya Wang (Arthropod-Plant Interactions, 2024)

Atlas and source of the microplastics of male reproductive system in human and mice - Wen Yang; Longmei Wu; Guanjian Li; Lan Shi; Junqiang Zhang; Liting Liu; Yuge Chen; Hui Yu; Kai Wang; Lei Xin; Dongdong Tang; Qunshan Shen; et al. (Environmental Science and Pollution Research, 2024)

Glyphosate exposure affected longevity-related pathways and reduced survival in asian honey bees (Apis cerana) - Dong Zhi-Xiang; Li Wan-Li; LI Xi-Jie; Li Jia-Li; Zhang Jun; Zhao Chong-Hui; Huang Qi; Cao Zhe; Chen Yuan; Zhao Hong-Mu; Guo Jun; Tian Wen-Li (Chemosphere, 2024)

Physiological, transcriptome and gene functional analysis provide novel sights into cadmium accumulation and tolerance mechanisms in kenaf - Shan Cao; Meng Wang; Jiao Pan; Dengjie Luo; Samavia Mubeen; Caijin Wang; Jiao Yue; Xia Wu; Qijing Wu; Hui Zhang; Canni Chen; Muzammal Rehman; et al. (Journal of Environmental Sciences, 2024)

Characterization and the mechanism underlying the cryoprotective activity of a peptide from large yellow croaker (Pseudosciaena crocea) - Zhe Xu; ShengAo Cao; Zhixuan Zhu; Bing Hu; Hui Chen; Maolin Tu; Zhijian Tan; Ming Du; Tingting Li (Food Chemistry, 2024)

Long-Term Application of Chinese Milk Vetch Return to Soil Alters Phosphorus forms Associated with Aggregates - Hui Wang; Shan Tang; Shang Han; Wenlong Cheng; Rongyan Bu; Min Li; Wu Ji; Weidong Cao (Journal of Soil Science and Plant Nutrition, 2024)

Changes of sediment provenance driven by the sea level and Indian summer monsoon in the northern Ninetyeast Ridge over the past 50 kyr - Wenjing Qi; Shengfa Liu; Xiaoyan Li; Hui Zhang; Peng Cao; Xuefa Shi; Dejiang Fan; Zhengxin Yin; Liang Chen (Journal of Asian Earth Sciences, 2024)

Tailoring local environment of oxygen vacancies by molybdenum doping on MnO2 for enhanced catalytic oxidation of VOCs - Yarui Qiao; Shu Yang; Xiaoxia Sun; Cao Liu; Zhilou Liu; Xinxin Li; Lingling Li; Hui Liu; Lei Wang (Chemical Engineering Journal, 2024)

Comparison of phosphorus migration and transformation characteristics in sediments of lakes within the Yangtze River basin and reservoirs on the Wujiang River - Hui Li; Yingying Cai; Chunlei Song; Zhong Cao; Ji Li; Zhenhua Qin; Shunxi Zhang; Jianfen Li; Xiuyun Cao; Yiyong Zhou (Journal of Soils and Sediments, 2024)

Development and experimental validation of a machine learning-based disulfidptosis-related ferroptosis score for hepatocellular carcinoma - Cong Zhang; Tiantian Xu; Kun Ji; Shoujin Cao; Jing Ai; Junhan Pan; Yunbo Cao; Yuning Yang; Li Jing; Jun-Hui Sun (Apoptosis, 2024)

A comprehensive review of food gels: formation mechanisms, functions, applications, and challenges - Bin Liu; Haixia Yang; Chenhui Zhu; Jianbo Xiao; Hui Cao; Jesus Simal-Gandara; Yujin Li; Daidi Fan; Jianjun Deng (Critical Reviews in Food Science and Nutrition, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Oral phages prophylaxis against mixed Escherichia coli O157:H7 and Salmonella Typhimurium infections in weaned piglets - Lei Li; Kaiou Han; Xinyu Mao; Leping Wang; Yajie Cao; Ziyong Li; Yuxing Wu; Yizhou Tan; Yan Shi; Lili Zhang; Hui Liu; Yinan Li; et al. (Veterinary Microbiology, 2024)

Multiomics was used to clarify the mechanism by which air pollutants affect chronic obstructive pulmonary disease: A human cohort study - Huijun Li; Yanting Yang; Yanpeiyue Yang; Chengkai Zhai; Juan Yao; Wei Liao; Yongbin Wang; Jing Wang; Chenlong Cao; Hany W. Darwish; Wei Wu; Wenlong Li; et al. (Toxicology, 2024)

Beyond contamination: Enhancing plant tolerance to arsenic through phytobial remediation - Saeed ur Rahman; Xinxin Liu; Muhammad Khalid; Asad Rehman; Junfeng Cao; Sadaf-Ilyas Kayani; Muhammad Naeem; Naveed Ahmad; Abid Ali Khan; Muhammad Aamir Manzoor; Chang Zhao; Haoxin Tan; et al. (South African Journal of Botany, 2024)

Assessment of heavy metals concentrations in five marine organisms from Lianyungang in China and the corresponding health risk - Ya-Qin Zhang; Chun-Hui Gong; Xiang-Hua Qi; Wen-Jun Wang; Peng-Tao Cao; Qiang Li; Peng Wang; Yi Yang (Regional Studies in Marine Science, 2024)

Spatial and temporal distributions of clay minerals in the central Andaman Sea: Provenances and sedimentary processes over the last 42 kyr - Peng Cao; Shengfa Liu; Xisheng Fang; Hui Zhang; Xiaoyan Li; Gang Yang; Somkiat Khokiattiwong; Narumol Kornkanitnan; Xuefa Shi (Journal of Asian Earth Sciences, 2024)

Petrogenesis of magnesian troctolitic granulite clasts from Chang'e -5 drilling sample: Implications for the origin of ejecta material from lunar highlands - Qi He; Zhi Cao; Yuqi Qian; Hejiu Hui; Ioannis Baziotis; Long Xiao; Zaicong Wang; Biji Luo; Yiheng Li; Zongjun Ying; Yang Li (Icarus, 2024)

A nanocarrier immersion vaccine encoding surface immunogenic protein confers cross-immunoprotection against Streptococcus agalactiae and Streptococcus iniae infection in tilapia - Ye Cao; Jia Liu; Gaoyang Liu; Hui Du; Tianqiang Liu; Tao Liu; Pengfei Li; Qing Yu; Gaoxue Wang; Erlong Wang (Fish & Shellfish Immunology, 2024)

Active/passive protection and anti-UV waterborne epoxy coatings based on low defect functionalized PDA-GO-CeO2 material for excellent corrosion control - Hao Li; Qin-Hao Zhang; Xian-Ze Meng; Hao-Jie Yan; Hui-Song Hu; Lian-Kui Wu; Fa-He Cao (Chemical Engineering Journal, 2024)

Retraction Note to: Mesothelial cells differentiate into fibroblast-like cells under the scirrhous gastric cancer microenvironment and promote peritoneal carcinomatosis in vitro and in vivo - Zhi-Dong Lv; Hai-Bo Wang; Qian Dong; Bin Kong; Jian-guo Li; Zhao-Chuan Yang; Hui-Li Qu; Wei-Hong Cao; Hui-Mian Xu (Molecular and Cellular Biochemistry, 2024)

Study on the Sand-Scouring Characteristics of Pulsed Submerged Jets Based on Experiments and Numerical Methods - Hongliang Wang; Xuanwen Jia; Chuan Wang; Bo Hu; Weidong Cao; Shanshan Li; Hui Wang (Journal of Marine Science and Engineering, 2023)
Water-jet-scouring technology finds extensive applications in various fields, including marine engineering. In this study, the pulse characteristics are introduced on the basis of jet-scouring research, and the sand-scouring characteristics of a pulsed jet under different Reynolds numbers and the impact distances are deeply investigated using Flow-3D v11.2. The primary emphasis is on the comprehensive analysis of the unsteady flow structure within the scouring process, the impulse characteristics, and the geometric properties of the resulting scouring pit. The results show that both the radius and depth of the scour pit show a good linear correlation with the jet-flow rate. The concentration of suspended sediment showed an increasing and then decreasing trend with impinging distance. The study not only helps to enrich the traditional theory of jet scouring, but also provides useful guidance for engineering applications, which have certain theoretical and practical significance.

Trade-offs between ligninase and cellulase and their effects on soil organic carbon in abandoned Moso bamboo forests in southeast China - Yaowen Xu; Yan Zhou; Hui Wang; Xiaogai Ge; Ge Gao; Yonghui Cao; Zhengcai Li; Benzhi Zhou (Science of The Total Environment, 2023)

Integrated multifunctional nanoplatform for fluorescence detection and inactivation of Staphylococcus aureus - Jing-bo Jiao; Qing Kang; Jiang-li Cao; Shuai-qi Zhang; Chen-jing Ma; Tong Lin; Ze-hui Xiao; Chu-min Zhao; Ting Du; Xin-jun Du; Shuo Wang (Food Chemistry, 2023)

Implicit finite difference wave equation forward modeling based on partial fraction expansion - Jian-yong Song; Hong Cao; Ming-hui Lu; Zhi-fang Yang; Xin-hai Hu; Hong-bing Li; Xin-fei Yan (Applied Geophysics, 2023)

Enolase-based nanovaccine immersion immunization induces robust immunity and protection against Streptococcus infection in tilapia - Jia Liu; Ye Cao; Haixiang Ma; Hui Du; Tianqiang Liu; Gaoxue Wang; Mingzhu Liu; Qing Wang; Pengfei Li; Erlong Wang (Aquaculture, 2023)

The resistance of the jujube (Ziziphus jujuba) to the devastating insect pest Apolygus lucorum (Hemiptera, Insecta) involves the jasmonic acid signaling pathway - Qingliang Li; Zujun Yin; Wei Tan; Xia Sun; Hui Cao; Deya Wang (Pesticide Biochemistry and Physiology, 2023)

Spatiotemporal dynamics of phytoplankton biomass and community succession for driving factors in a meso-eutrophic lake - Jing Cao; Ze-ying Hou; Ze-kun Li; Bing-hui Zheng; Zhao-sheng Chu (Journal of Environmental Management, 2023)

Chemical weathering patterns driven by solar insolation and Indian monsoon in the southern Bay of Bengal since the last glaciation - Hui Zhang; Shengfa Liu; Peng Cao; Wenxing Ye; Jingrui Li; Xingquan Sun; Xiaoyan Li; Hongmin Wang; Somkiat Khokiattiwong; Narumol Kornkanitnan; Xuefa Shi (Journal of Asian Earth Sciences, 2023)

Characterizing nighttime vertical profiles of atmospheric particulate matter and ozone in a megacity of south China using unmanned aerial vehicle measurements - Zhanyong Wang; Ruhui Cao; Bai Li; Ming Cai; Zhong-Ren Peng; Guohua Zhang; Qingchang Lu; Hong-di He; Jinpu Zhang; Kai Shi; Yonghong Liu; Hui Zhang; et al. (Environmental Research, 2023)

A 4.43-Kb deletion of chromosomal segment containing an ovate family protein confers long capsule in sesame (Sesamum indicum L.) - Cuiying Wang; Jiaojiao Niu; Libin Wei; Chun Li; Guiting Li; Qiuzhen Tian; Ming Ju; Qin Ma; Hengchun Cao; Yinghui Duan; Hui Guo; Haiyang Zhang; et al. (Theoretical and Applied Genetics, 2023)

Cellulose nanofibrils/polyvinyl alcohol gel microspheres loaded with nickel nanoparticles as catalysts to reduce Cr (VI) by formic acid - Yuhang Li; Hui Cao; Lingyun Jia; Wenli Liu; Pengtao Liu (Clean Technologies and Environmental Policy, 2023)

Quantitative calculation of gases generation during low-temperature oxidation of coal - Jinhu Li; Qin Cao; Wei Lu; Jingjuan Geng; Jinliang Li; Hui Zhuo (Environmental Science and Pollution Research, 2023)

A Long-Term Operational Scheme for Hybrid Hydro-Photovoltaic (PV) Systems that Considers the Uncertainties in Reservoir Inflow and Solar Radiation Based on Scenario Trees - Han Cao; Jun Qiu; Hui-Min Zuo; Fang-Fang Li (Water Resources Management, 2023)

On the distributed blowing control of flow around a square cylinder at a low Reynolds number - Yize Ran; Wen-Li Chen; Yong Cao; Hui Li; Donglai Gao (Ocean Engineering, 2023)

Selenium improves the medicinal safety and quality of Bletilla striata by promoting the fixation of cadmium in root: Pot and field experiments - Na Li; Li Yang; Kuiwei Chen; Yuchen Kang; Yuan Cao; Hengwei Du; Haiyan Mou; Hui Sun; Tianqi Ao; Wenqing Chen (Journal of Hazardous Materials, 2023)

How to develop site-specific waterlogging mitigation strategies? Understanding the spatial heterogeneous driving forces of urban waterlogging - Qifei Zhang; Zhifeng Wu; Zheng Cao; Guanhua Guo; Hui Zhang; Cheng Li; Paolo Tarolli (Journal of Cleaner Production, 2023)

Halide-free squaramide–phenolate organocatalyst for the cycloaddition of CO2 into epoxides - Bo Liu; Hui Yu; Zhenjiang Li; Jun He; Yongzhu Hu; Xin Zou; Longlin Lu; Shaoju Cao; Canliang Ma; Kai Guo (Journal of Environmental Chemical Engineering, 2023)

Geochemical records provide evidences for the evolution of the marine redox environment in the southwestern Sumatra waters over the past 35,000 years - Hui Zhang; Shengfa Liu; Peng Cao; Ziye Li; Rainer Arief Troa; Rina Zuraida; Eko Triarso; Marfasran Hendrizan; Xuefa Shi (Journal of Asian Earth Sciences, 2023)

Effects of long-term substitution of chemical fertilizer with Chinese milk vetch on soil phosphorus availability and leaching risk in the double rice systems of Eastern China - Hui Wang; Shan Tang; Shang Han; Min Li; Wenlong Cheng; Rongyan Bu; Weidong Cao; Ji Wu (Field Crops Research, 2023)

Developing TADF polymer as semiconductor additive for high performance perovskite light emitting diodes with dual recombination channel and small efficiency roll-off - Xinxin Ban; Qingpeng Cao; Wei Yang; Wenhao Zhang; Hui Xu; Jiayi Wang; Xiuwang Li; Chunhong Gao (Chemical Engineering Journal, 2023)

Potential xylose transporters regulated by CreA improved lipid yield and furfural tolerance in oleaginous yeast Saitozyma podzolica zwy-2-3 - Yulu Ran; Qingzhuoma Yang; Jie Zeng; Fazhi Li; Yu Cao; Qingrui Xu; Dairong Qiao; Hui Xu; Yi Cao (Bioresource Technology, 2023)

Genome-wide identification of CUC gene family and functional analysis of HcCUC1 in kenaf - Qijing Wu; Canni Chen; Jiao Yue; Samavia Mubeen; Shan Cao; Xin Li; Meng Wang; Hui Zhang; Xia Wu; Caijin Wang; Dengjie Luo; Peng Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

Southern China can produce more high-quality rice with less N by green manuring - Songjuan Gao; Guopeng Zhou; Danna Chang; Hao Liang; Jun Nie; Yulin Liao; Yanhong Lu; Changxu Xu; Jia Liu; Ji Wu; Shang Han; Hui Wang; et al. (Resources, Conservation and Recycling, 2023)

Review: WRKY transcription factors: Understanding the functional divergence - Hui Song; Yunpeng Cao; Longgang Zhao; Jiancheng Zhang; Shuai Li (Plant Science, 2023)

Dictamnine suppresses the development of pear ring rot induced by Botryosphaeria dothidea infection by disrupting the chitin biosynthesis - Minxuan Yuan; Xiaogui Liang; Duantao Cao; Hongliang Wu; Suling Xiao; Hui Liang; Hang Li; Yingjin Huang; Hongyi Wei; Wenwen Peng; Xiaoxiang Fu (Pesticide Biochemistry and Physiology, 2023)

Genetic diversity, antibiotic resistance, and virulence characteristics of Staphylococcus aureus from raw milk over 10 years in Shanghai - Jiewen Huang; Wengang Zhang; Bingqing Sun; Qin Jiang; Ying Cao; Jun Shang; Yu Zhang; Xin Gu; Chao Lv; Chaoyi Guo; Min Li; Hui Li; et al. (International Journal of Food Microbiology, 2023)

Molecular characterization and expression of twenty interleukin-17 transcripts in the common Chinese cuttlefish (Sepiella japonica) in response to Vibrio harveyi infection - Xu Zhou; Pei-Xuan Fang; Hui-Min Cao; Jian-Jun Xie; Shuang Li; Chang-Feng Chi (Fish & Shellfish Immunology, 2023)

S-scheme Co3(PO4)2/Twinned-Cd0.5Zn0.5S homo-heterojunction for enhanced photocatalytic H2 evolution - Jingzhuo Tian; Xiaofei Cao; Tao Sun; Jun Fan; Hui Miao; Zhong Chen; Dong Li; Enzhou Liu; Yonghong Zhu (Chemical Engineering Journal, 2023)

Continuous Co-incorporation of Chinese Milk Vetch and Rice Straw with Reduced Chemical Fertilizer Maintains Rice Yield as a Consequence of Increased Carbon and Nitrogen Storage in Soil Aggregates - Rongyan Bu; Wenlong Cheng; Shang Han; Run Hu; Hui Wang; Shan Tang; Min Li; Qin Zhu; Ji Wu; Weidong Cao (Journal of Soil Science and Plant Nutrition, 2023)

One-step leaching mechanism for total elemental recovery from spent lithium-ion batteries utilizing ethylene diamine tetraacetic acid - Fanyun Su; Qi Meng; Xiangyang Zhou; Xiaojian Liu; Juan Yang; Jingjing Tang; Wan Yang; Penghui Cao; Zhenxiao Li; Hui Wang; Yayun Ma (Journal of Environmental Chemical Engineering, 2023)

Ejiao peptide-iron chelates regulate the metabolism of iron deficiency anemia mice and improve the bioavailability of iron - Xiang-Rong Cheng; Yu-Yao Chen; Cong-Cong Cao; Jia-Hui Ma; Chen-Xi Zhang; Zi-Wei Zhao; Qian Wu; Yuan-Yuan Li; Mitchell N. Muskat; Guo-Qing Wu (Food Bioscience, 2023)

Detailed study on the regeneration of CoS2 loaded porous carbon for elemental mercury removal from flue gas - Junyuan Li; Kaisong Xiang; Cao Liu; Shudan He; Fenghua Shen; Hui Liu (Chemical Engineering Journal, 2023)

Arsenic Induces Blood‒Brain Barrier Disruption and Regulates T Lymphocyte Subpopulation Differentiation in the Cerebral Cortex and Hippocampus Associated with the Nrf2 Pathway In Vivo - Nan Yan; Hui Jing; Jie Wang; Zhou Li; Kangjie Xu; Qian Wang; Jingwen Zheng; Lei Shi; Xiankui Cao; Xiaoxu Duan (Biological Trace Element Research, 2023)

Biological characteristics and genomic analysis of a novel Escherichia phage Kayfunavirus CY1 - Yajie Cao; Dongxin Ma; Yuqing Zhou; Leping Wang; Kaiou Han; Lei Li; Xinyu Mao; Ziyong Li; Yuxin Wu; Hui Liu; Yizhou Tan; Xun Li (Virus Genes, 2023)

Impact of climate-driven oasis evolution on human settlement in the Baiyang River Basin, northwest China, Hami, during the middle to late Holocene - Aijun Sun; Haoran Li; Shanjia Zhang; Huihui Cao; Menghan Qiu; Yongqiang Wang; Bing Liu; Hui Zhao; Guanghui Dong (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

3-D Crosswell electromagnetic inversion based on IRLS norm sparse optimization algorithms - Ligang Cao; Xiaocui Li; Hui Cao; Lei Liu; Tongbiao Wei; Xintao Yang (Journal of Applied Geophysics, 2023)

Identification of the design point based on Monte Carlo simulation - Guo-Hui Gao; Dian-Qing Li; Zi-Jun Cao (Computers and Geotechnics, 2023)

Resveratrol and Sir2 Reverse Sleep and Memory Defects Induced by Amyloid Precursor Protein - Yuping Hao; Lingzhan Shao; Jianan Hou; Yan Zhang; Yuqian Ma; Jinhao Liu; Chuan Xu; Fujun Chen; Li-Hui Cao; Yong Ping (Neuroscience Bulletin, 2023)

Different characteristics of sediment nitrogen and phosphorus recycling during cyanobacterial growth and their succession - Hui Li; Chunlei Song; Daizhong Huang; Wenjuan Shen; Yun He; Jianfen Li; Xiuyun Cao; Yiyong Zhou (Journal of Soils and Sediments, 2023)

Advance toward isolation, extraction, metabolism and health benefits of kaempferol, a major dietary flavonoid with future perspectives - Li Yang; Yongchao Gao; Vivek K. Bajpai; Heba A. El-Kammar; Jesus Simal-Gandara; Hui Cao; Ka-Wing Cheng; Mingfu Wang; Randolph R. J. Arroo; Liang Zou; Mohamed A. Farag; Yonghua Zhao; et al. (Critical Reviews in Food Science and Nutrition, 2023)

The BrAFP1 promoter drives gene-specific expression in leaves and stems of winter rapeseed (Brassica rapa L.) under cold induction - Xiaoyun Dong; Zigang Liu; Jiaping Wei; Guoqiang Zheng; Hui Li; Ying Wang; Haiyan Tian; Junmei Cui; Zefeng Wu; Xiaodong Cao; Chunmei Xu (Plant Science, 2023)

Physiological and DNA methylation analysis provides epigenetic insights into kenaf cadmium tolerance heterosis - Dengjie Luo; Hai Lu; Caijin Wang; Samavia Mubeen; Shan Cao; Jiao Yue; Jiao Pan; Xia Wu; Qijing Wu; Hui Zhang; Canni Chen; Muzammal Rehman; et al. (Plant Science, 2023)

Metformin Alleviates Delayed Hydrocephalus after Intraventricular Hemorrhage by Inhibiting Inflammation and Fibrosis - Yi Cao; Chang Liu; Gaowei Li; Weina Gao; Hui Tang; Shuanmin Fan; Xin Tang; Long Zhao; Haoxiang Wang; Aijun Peng; Chao You; Aiping Tong; et al. (Translational Stroke Research, 2023)

Geminivirus satellite-encoded βC1 activates UPR, induces bZIP60 nuclear export, and manipulates the expression of bZIP60 downstream genes to benefit virus infection - Mingzhen Zhang; Buwei Cao; Hui Zhang; Zaifeng Fan; Xueping Zhou; Fangfang Li (Science China Life Sciences, 2023)

Effects of Bacillus subtilis BS-Z15 on Intestinal Microbiota Structure and Body Weight Gain in Mice - Jun Yang; Huan-Chen Ning; Qi Zhang; Jun-Qi Yue; Xi-Yuan Cao; Jin-Yu Li; Ling Liu; He-Ping Zhao; Hui-Xin Zhao (Probiotics and Antimicrobial Proteins, 2023)

Comparative Physiological and Transcriptomic Analysis Provide New Insights of Crucial Pathways and Genes Regulating Kenaf Salt Tolerance - Yali Hu; Zengqiang Li; Meiqiong Tang; Dengjie Luo; Muhammad Haneef Kashif; Shan Cao; Caijin Wang; Jiao Yue; Zhen Huang; Jiao Pan; Xia Wu; Qijing Wu; et al. (Journal of Plant Growth Regulation, 2023)

Effects of kaolin particle film coatings on the water-saving efficiency and fruit quality of Cabernet Sauvignon (Vitis vinifera L.) grape plants in the Ningxia region of China - Xiao Cao; Ying Wang; Zhi-Lei Wang; Xue-Lin Tian; Xing Han; Dong Wu; Fei Yao; Miao Hui; Hua Li; Hua Wang (Horticulture, Environment, and Biotechnology, 2023)

Spatialization of Chinese R-410A emissions from the room air-conditioning sector - Pengcheng Wu; Li Zhang; Bo Yao; Bofeng Cai; Yifang Zhu; Hui Liu; Pengling Wang; Lisha Liu; Yanwei Dou; Han Yan; Yijun Liu; Zixuan Xie; et al. (Environment, Development and Sustainability, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Improving the biodegradation of chicken feathers by a Bacillus licheniformis ZSZ6 mutant and application of hydrolysate - Chunhong Cui; Liqiong Sun; Xuelian Chen; Yu Zhu; Zhi Zheng; Dongmei Mao; Mingxu Li; Yuxin Li; Yajun Cao; Bing Feng; Hui Wang; Lin Wang; et al. (International Biodeterioration & Biodegradation, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Stimulation of atrazine degradation by activated carbon and cathodic effect in soil microbial fuel cell - Hui Wang; Xizi Long; Xian Cao; Lei Li; Jingran Zhang; Yaqian Zhao; Dongqi Wang; Zhe Wang; Haiyu Meng; Wen Dong; Chunbo Jiang; Jiake Li; et al. (Chemosphere, 2023)

Bioaccessibility and bioavailability of NPAHs in soils using in vitro-in vivo assays: Comparison of laboratory and outdoor environmental aging effect - Xian-Xian Chen; Chao Li; Xiao-Yu Cao; Krishna Kumar Selvaraj; Hui-Ming Li; Feng-Xiao Zhu; Shao-Gui Yang; Shi-Yin Li; Li-Min Zhang; Huan He (Science of The Total Environment, 2023)

Magnetic field assisted enhancement of electronic metal-support interactions in FexCuy@TiO2-δ catalysts for arsine catalytic oxidation - Yibing Xie; Xueqian Wang; Ping Ning; Langlang Wang; Yixing Ma; Yuan Li; Rui Cao; Hui Zhang; Xiang Li; Bowen Xu (Journal of Cleaner Production, 2023)

Advantageous Role of N-doping on K@Al in COS/CS2 Hydrolysis: Diminished Oxygen Mobility and Rich basic sites - Rui Cao; Xueqian Wang; Ping Ning; Yibing Xie; Langlang Wang; Yixing Ma; Xiang Li; Hui Zhang; Jingye Liu (Fuel, 2023)

Characterization and genome analysis of a novel phage Kayfunavirus TM1 - Kaiou Han; Xinyu Mao; Hui Liu; Yuxing Wu; Yizhou Tan; Ziyong Li; Runwen Ma; Yinan Li; Lei Li; Leping Wang; Yan Shi; Yajie Cao; et al. (Virus Genes, 2023)

An environmentally insensitive fluorescent probe for G4 DNA detection: Design, synthesis, and mechanism studies - Xue-Xian Lang; Shu-Hui Sun; Hao-Wen Cao; Yan-Song Chen; Hong-Yao Li; Ming-Qi Wang (Analytica Chimica Acta, 2023)

Trophic transfer of polycyclic aromatic hydrocarbons through the food web of the Fildes Peninsula, Antarctica - Shuaichen Jin; Shengkai Cao; Ruijing Li; Hui Gao; Guangshui Na (Environmental Science and Pollution Research, 2023)

Comparative transcriptome analysis of non-germinated and germinated spores of Enterocytozoon hepatopenaei (EHP) in vitro - Yabin Dou; Leiting Zhang; Hui Shen; Sheng Zhang; Xiaohui Cao; Yi Qiao; Ge Jiang; Jie Cheng; Xihe Wan; Xianping Fan; Hui Li; Libao Wang; et al. (Journal of Invertebrate Pathology, 2023)

Potential of crop straw incorporation for replacing chemical fertilizer and reducing nutrient loss in Sichuan Province, China - Ying Wang; Bang-qiang Liang; Hui Bao; Qian Chen; Ya-lei Cao; Yan-qing He; Liang-zhong Li (Environmental Pollution, 2023)

Self-sufficient biocatalysts constructed using chitin-based microspheres - Ning Zhou; Guoguang Wei; Xueman Chen; Bin Wu; Hui Li; Qiuhao Lu; Xun Cao; Alei Zhang; Kequan Chen; Pingkai Ouyang (Chemical Engineering Journal, 2023)

Hydraulic determinants of drought-induced tree mortality and changes in tree abundance between two tropical forests with different water availability - Yong-Qiang Wang; Hui-Qing Song; Ya-Jun Chen; Pei-Li Fu; Jiao-Lin Zhang; Kun-Fang Cao; Shi-Dan Zhu (Agricultural and Forest Meteorology, 2023)

Dietary pattern interfered with the impacts of pesticide exposure by regulating the bioavailability and gut microbiota - Ai Song Chen; Dong Hui Liu; Hao Nan Hou; Jia Ning Yao; Shou Chun Xiao; Xiao Ran Ma; Pei Ze Li; Qian Cao; Xue Ke Liu; Zhi Qiang Zhou; Peng Wang (Science of The Total Environment, 2023)

Four new Myrioneuron alkaloids from Mycetia effusa (Myrioneuron effusum) - Xiao-Hui Li; Jia-Hui Zhang; Yu Zhang; Ying-Tong Di; Yu-Cheng Gu; Mingming Cao; Xiao-Jiang Hao (Phytochemistry Letters, 2023)

2000 years of lake-level fluctuations and human adaptation around China's largest freshwater lake - Huanye Wang; Weiguo Liu; Qin Leng; Lin Yang; Hui Zhao; Jun Yang; Yuwei Chen; Shangbin Xiao; Yunning Cao; Jing Hu; Xiaoke Qiang; Peng Cheng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Oil diffusion mathematical model in oily sludge particle under supercritical water environment - Gaoyun Wang; Le Wang; Linhu Li; Yunan Chen; Wen Cao; Hui Jin; Zhiwei Ge; Liejin Guo (Journal of Hazardous Materials, 2023)

Simultaneous removal of sediment and water contaminants in a microbial electrochemical system with embedded active electrode by in-situ utilization of electrons - Xian Cao; Chong Zhang; Shuai Zhang; Takashi Sakamaki; Hui Wang; Xian-Ning Li (Journal of Hazardous Materials, 2023)

Experimental study on alkali catalytic gasification of oily sludge in supercritical water with a continuous reactor - Linhu Li; Gaoyun Wang; Xujun Li; Le Wang; Jiawei Zhang; Ke Cheng; Pai Peng; Wen Cao; Hui Jin; Liejin Guo (Journal of Environmental Management, 2023)

Microbiological analysis and characterization of Salmonella and ciprofloxacin-resistant Escherichia coli isolates recovered from retail fresh vegetables in Shaanxi Province, China - Chenyang Cao; Wenxing Zhao; Zexun Lü; Yixin Mo; Wei Hu; Shengyuan Sun; Huabin Cheng; Jiaqi Ma; Sirui Xiong; Xiaorong Jin; Hui Yang; Li Bai; et al. (International Journal of Food Microbiology, 2023)

Rapid charge transfer in covalent organic framework via through-bond for enhanced photocatalytic CO2 reduction - Li-Juan Gong; Li-Yao Liu; Shao-Shuai Zhao; Shuai-Long Yang; Duan-Hui Si; Qiu-Jin Wu; Qiao Wu; Yuan-Biao Huang; Rong Cao (Chemical Engineering Journal, 2023)

Repaired surface structural imperfection of tin Wide-Bandgap perovskite films for photovoltaic application - Tian-Yu Teng; Fan Hu; Yan-Hui Lou; Jun-Jie Cao; Chun-Hao Chen; Yi-Ran Shi; Kai-Li Wang; Jing Chen; Zhao-Kui Wang; Liang-Sheng Liao (Chemical Engineering Journal, 2023)

Ultra-facile fabrication of oxygen vacancy-laden catalyst for peroxymonosulfate activation to degrade organic pollutant in water: Performance and mechanism - Hanxiao Chen; Zhaoyi Han; Shiyi Cao; Yinghao Li; Xin Kang; Cheng Cheng; Xuantong Chen; Yin Xu; Hui Zhang (Chemical Engineering Journal, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Sediment provenances shift driven by sea level and Indian monsoon in the southern Bay of Bengal since the last glacial maximum - Shengfa Liu; Wenxing Ye; Hui Zhang; Peng Cao; Jingrui Li; Xingquan Sun; Xiaoyan Li; Xisheng Fang; Somkiat Khokiattiwong; Narumol Kornkanitnan; Xuefa Shi (Frontiers in Marine Science, 2023)
The Tibetan Plateau uplift has induced the formation of the largest sediment source-sink system in the northeast Indian Ocean, which has become an ideal region for investigating land-sea interaction processes. However, many questions regarding sediment transport patterns and their controlling factors at different time scales remain unanswered. Therefore, in the present study, a gravity core named BoB-79, based on the southern Bay of Bengal (BoB) was selected to investigate sediment provenance shift and its corresponding mechanism to sedimentary environment change since the last glacial maximum (LGM). The clay mineral compositions are analyzed and the whole core sediments reveal a feature dominated by illite (~55%), followed by chlorite (~24%) and kaolinite (~17%), and the content of smectite (~4%) is the lowest. A trigonometric analysis of provenance discrimination of clay minerals showed that the Himalayas, together with the Indian Peninsula, represent the main sources of southern BoB sediments, and the last glacial period might have been controlled by the dominant Himalayan provenance, with an average contribution of approximately 90%. However, as a secondary source, the influence of the Indian Peninsula increased significantly during the Holocene, and its mean contribution was 24%, thus, indicating that it had a crucial effect on the evolution process of BoB. The sediment transportation pattern changed significantly from the LGM to the Holocene: in the last glacial period, the low sea level exposed the shelf area that caused the Ganges River connected with the largest submarine canyon in BoB named Swatch of No Ground (SoNG), and the Himalayan materials could be transported to the BoB directly under a strong turbidity current, thereby forming the deep sea deposition center with a sedimentation rate of 4.5 cm/kyr. Following Holocene, the sea level increased significantly, and the materials from multiple rivers around the BoB were directly imported into the continental shelf area. The intensive Indian summer monsoon dominated the transportation process of the terrestrial materials, thereby forming a deposition center in the shallow water area of the continental shelf northeast Indian Ocean; subsequently, the material flux relative to the input to the deep sea area decreased significantly, and the sedimentation rate in the southern BoB decreased to 1.7 cm/kyr.

Trace elements in red swamp crayfish (Procambarus clarkii) in China: Spatiotemporal variation and human health implications - Hui Li; Huaiyan Li; Haiting Zhang; Jing Cao; Tao Ge; Jiale Gao; Yan Fang; Wenling Ye; Ting Fang; Yanhong Shi; Rong Zhang; Xinju Dong; et al. (Science of The Total Environment, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

Variability of thermocline temperature in the Bay of Bengal and its response to solar insolation and Indian monsoon over the last 15 kyr - Shengfa Liu; Wenxing Ye; Hui Zhang; Peng Cao; Jingrui Li; Xiaoyan Li; Somkiat Khokiattiwong; Narumol Kornkanitnan; Xuefa Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

L-cysteine boosted Fe(III)-activated peracetic acid system for sulfamethoxazole degradation: Role of L-cysteine and mechanism - Yinhao Dai; Hui Cao; Chengdu Qi; Yijie Zhao; Yanni Wen; Chenmin Xu; Qiang Zhong; Dunyu Sun; Shuohua Zhou; Bing Yang; Shaogui Yang; Huan He; et al. (Chemical Engineering Journal, 2023)

N2O emissions from soils under short-term straw return in a wheat-corn rotation system are associated with changes in the abundance of functional microbes - Jitong Lin; Zhiyu Xu; Yinghao Xue; Renhua Sun; Rongguang Yang; Xiaoxu Cao; Hui Li; Qi Shao; Yanhong Lou; Hui Wang; Quangang Yang; Hong Pan; et al. (Agriculture, Ecosystems & Environment, 2023)

Shanghai Autism Early Development: An Integrative Chinese ASD Cohort - Yuan Dai; Yuqi Liu; Lingli Zhang; Tai Ren; Hui Wang; Juehua Yu; Xin Liu; Zilin Chen; Lin Deng; Minyi Tao; Hangyu Tan; Chu-Chung Huang; et al. (Neuroscience Bulletin, 2022)

Uncovering expression and functional analysis of newly discovered high-affinity K+ transporter family members from sugarcane - Hai-bin Luo; Cheng-mei Huang; Yuan-wen Wei; Hui-ming Zhu; Hui-qing Cao; Sheng-li Jiang; Zhi-nian Deng; Kai-chao Wu; Lin Xu (Journal of Plant Biochemistry and Biotechnology, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

Caffeine alleviates acute liver injury by inducing the expression of NEDD4L and deceasing GRP78 level via ubiquitination - Xing-Wang Hu; Xiang-Min Li; Ai-Min Wang; Yong-Ming Fu; Fang-Jie Zhang; Feng Zeng; Li-Ping Cao; Hui Long; Ying-Hui Xiong; Ji Xu; Jia Li (Inflammation Research, 2022)

Differential expression and functional analysis of circRNA in the ovaries of Yili geese at different egg-laying stages - Xiao-yu Zhao; Ying-ping Wu; Hai-ying Li; Yan Cao; Zhi-yong Mei; Jia-hui Li (Genes & Genomics, 2022)

Genetic Control of the Root System Traits in Oilseed Rape Under Contrasting Phosphate Supply Conditions by Genome-wide Association Study - Ping Xu; Xiaohua Wang; Hui Li; Shengjie Dai; Xue Cao; Zhenning Liu (Plant Molecular Biology Reporter, 2022)

Relationship between maternal heavy metal exposure and congenital heart defects: a systematic review and meta-analysis - Shimeng Li; Qinbo Wang; Wenting Luo; Shanshan Jia; Dan Liu; Wei Ma; Hui Gu; Xiaowei Wei; Yiwen He; Songying Cao; Zhengwei Yuan (Environmental Science and Pollution Research, 2022)

Research on an Extensible Monitoring System of a Seafloor Observatory Network in Laizhou Bay - Jie Chen; Hailin Liu; Bin Lv; Chao Liu; Xiaonan Zhang; Hui Li; Lin Cao; Junhe Wan (Journal of Marine Science and Engineering, 2022)
An extensible remote monitoring system for a seafloor observatory network in Laizhou Bay was established to realize long-term, continuous and on-line monitoring for a marine ranching environment. This paper deals with data communication, device management and data quality control. A control model is introduced that is structured into four layers, enabling bidirectional information flow. Based on the control model, the standardized communication protocol and device object model-oriented dynamic management method are designed as plug-and-play, for data processing and control of a large number of devices. An improved data quality control method is proposed to reduce the data error rate. The monitoring system was developed based on socket network programming, MySQL database technologies and modular ideas. The seafloor observatory network was successfully deployed in Laizhou Bay marine ranching. The experimental results demonstrate that the monitoring system obtains better performance. The proposed algorithms can also be used in many other similar systems with adaptive requirements.

Relationship of night sleep duration with health lifestyle, depressive symptoms, internet addiction in Chinese High school Students - Yueyang Hu; Tingting Gao; Ruilin Cao; Hui Ren; Zeying Qin; Chuanen Li; Leilei Liang; Cuicui Meng; Xinmeng Guo; Jianping Lv; Songli Mei (Sleep and Biological Rhythms, 2022)

PPARγ Dysfunction in the Medial Prefrontal Cortex Mediates High-Fat Diet-Induced Depression - Cong-Cong Fu; Xin-Yi Zhang; Liu Xu; Hui-Xian Huang; Shuang Xu; Qiao-Qi Wu; Zhen Wang; Xi Gu; Li-Fang Lin; Song Lin; Ying-Ying Fang; Xiong Cao; et al. (Molecular Neurobiology, 2022)

Fullerene nanoparticles for the treatment of ulcerative colitis - Xiaodan Liao; Zhongpu Zhao; Hui Li; Bo Wu; Jiawei Huo; Lei Li; Xue Li; Xinran Cao; Min Xia; Chunru Wang; Chunli Bai (Science China Life Sciences, 2022)

Cloning and expressions of chop in loach (Misgurnus anguillicaudatus) and its response to hydrogen peroxide (H2O2) stress - Hui Li; Minxin Kang; Shouxiang Sun; Jian Gao; Zhiying Jia; Xiaojuan Cao (Fish Physiology and Biochemistry, 2022)

Reconstructed annual glacier surface mass balance in the Ányêmaqên Mountains, Yellow River source, based on snow line altitude - Kai-ji Li; Bo Cao; Wei-jin Guan; Bao-tian Pan; Dong-hui Shangguan (Journal of Mountain Science, 2022)

Ero1‐Pdi1 module‐catalysed dimerization of a nucleotide sugar transporter, FonNst2 , regulates virulence of Fusarium oxysporum on watermelon - Yizhou Gao; Xiaohui Xiong; Hui Wang; Jiajing Wang; Yan Bi; Yuqing Yan; Zhongye Cao; Dayong Li; Fengming Song (Environmental Microbiology, 2022)
Summary Fusarium oxysporum f. sp. niveum ( Fon ) is a soil‐borne fungus causing vascular Fusarium wilt on watermelon; however, the molecular network regulating Fon virulence remains to be elucidated. Here, we report the function and mechanism of nucleotide sugar transporters (Nsts) in Fon . Fon genome harbours nine FonNst genes with distinct functions in vegetative growth, asexual production, cell wall stress response and virulence. FonNst2 and FonNst3 are required for full virulence of Fon on watermelon and FonNst2 is mainly involved in fungal colonization of the plant tissues. FonNst2 and FonNst3 form homo‐ or hetero‐dimers but function independently in Fon virulence. FonNst2, which has UDP‐galactose transporter activity in yeast, interacts with FonEro1 and FonPdi1, both of which are required for full virulence of Fon . FonNst2, FonPdi1 and FonEro1 target to endoplasmic reticulum (ER) and are essential for ER homeostasis and function. FonEro1‐FonPdi1 module catalyses the dimerization of FonNst2, which is critical for Fon virulence. Undimerized FonNst2 is unstable and degraded via ER‐associated protein degradation in vivo . These data demonstrate that FonEro1‐FonPdi1 module‐catalysed dimerization of FonNst2 is critical for Fon virulence on watermelon and provide new insights into the regulation of virulence in plant fungal pathogens via disulfide bond formation of key pathogenicity factors.

Sex-specific mediation of placental inflammatory biomarkers in the effects of prenatal phthalate coexposure on preschooler cognitive development - Hui Gao; Juan Tong; Bei-bei Zhu; Meng-long Geng; Hong Gan; Li Sun; Xiao-yan Wu; Kun Huang; Hui Cao; Wen-wen Liu; Shu-man Tao; Peng Ding; et al. (Environmental Science and Pollution Research, 2022)

Triggering mechanism and dynamic process of water-rock flow in Nanfen waste dump in 2010 - Chun-hui Cao; Ji-li Feng; Zhi-gang Tao (Journal of Mountain Science, 2021)

Experimental study on integrated and autonomous conductivity-temperature-depth (CTD) sensor applied for underwater glider - Bin Lv; Hai-lin Liu; Yi-fan Hu; Cheng-xuan Wu; Jie Liu; Hai-jing He; Jie Chen; Jian Yuan; Zhao-wen Zhang; Lin Cao; Hui Li (Marine Georesources & Geotechnology, 2021)

Experimental investigation on synergetic prediction of rockburst using the dominant-frequency entropy of acoustic emission - Chunlai Wang; Cong Cao; Yubo Liu; Changfeng Li; Guangyong Li; Hui Lu (Natural Hazards, 2021)

A new epimer of azaphilone derivative pinophilin B from the gorgonian-derived fungus Aspergillus fumigatus 14–27 - Ya-Hui Zhang; Xiao-Yue Peng; Li-Xi Feng; Hua-Jie Zhu; Fei Cao; Chang-Yun Wang (Natural Product Research, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

The effect of land use change and soil redistribution on soil organic carbon dynamics in karst graben basin of China - Gaoyong Lan; Chun Liu; Hua Wang; Wei Tang; Xia Wu; Hui Yang; Linling Tu; Bill X. Hu; Jianhua Cao; Qiang Li (Journal of Soils and Sediments, 2021)

Ensemble machine learning to evaluate the in vivo acute oral toxicity and in vitro human acetylcholinesterase inhibitory activity of organophosphates - Liangliang Wang; Junjie Ding; Peichang Shi; Li Fu; Li Pan; Jiahao Tian; Dongsheng Cao; Hui Jiang; Xiaoqin Ding (Archives of Toxicology, 2021)

Altered structural and functional connectivity in CSF1R-related leukoencephalopathy - Fei-Xia Zhan; Ze-Yu Zhu; Qing Liu; Hai-Yan Zhou; Xing-Hua Luan; Xiao-Jun Huang; Xiao-Li Liu; Wo-Tu Tian; Shi-Ge Wang; Xiao-Xuan Song; Guang Chen; Ming-Liang Zhao; et al. (Brain Imaging and Behavior, 2021)

Delineating the organization of projection neuron subsets in primary visual cortex with multiple fluorescent rabies virus tracing - Liang Li; Yajie Tang; Leqiang Sun; Jinsong Yu; Siheng Zhang; Hui Gong; Hannah C. Webber; Xiaoyu Zhang; Zhe Hu; Xiangning Li; Khaista Rahman; Xiangwei Shi; et al. (Brain Structure and Function, 2021)

Selenium Supplementation Protects Against Lipopolysaccharide-Induced Heart Injury via Sting Pathway in Mice - Xuan Wang; Bin Yang; Hui-Li Cao; Rui-Ying Wang; Zhao-Yang Lu; Rui-Fang Chi; Bao Li (Biological Trace Element Research, 2021)

A Role of the Podoplanin-CLEC-2 Axis in Promoting Inflammatory Response After Ischemic Stroke in Mice - Danyang Meng; Xiaohua Ma; Hui Li; Xuechun Wu; Yongjun Cao; Zhigang Miao; Xia Zhang (Neurotoxicity Research, 2021)

Gas Flow Characteristics and Optimization of Gas Drainage Borehole Layout in Protective Coal Seam Mining: A Case Study from the Shaqu Coal Mine, Shanxi Province, China - Zhiheng Cheng; Hui Pan; Quanle Zou; Zhenhua Li; Liang Chen; Jialin Cao; Kun Zhang; Yongguo Cui (Natural Resources Research, 2021)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Curcumin protects thymus against D-galactose-induced senescence in mice - Jie-han Li; Ting-ting Wei; Li Guo; Jia-hui Cao; Yuan-kang Feng; Shu-ning Guo; Guo-hong Liu; Yi Ding; Yu-rong Chai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Accumulation of Cd by three forage mulberry (Morus atropurpurea Roxb.) cultivars in heavy metal–polluted farmland: a field experiment - Yongbing Jiang; Shimeng Jiang; Renzhi Huang; Ming Wang; Hui Cao; Zhangbao Li (Environmental Science and Pollution Research, 2021)

Observational study of super typhoon Meranti (2016) using satellite, surface drifter, Argo float and reanalysis data - Hui Chen; Shuang Li; Hailun He; Jinbao Song; Zheng Ling; Anzhou Cao; Zhongshui Zou; Wenli Qiao (Acta Oceanologica Sinica, 2021)

Production of functional human nerve growth factor from the submandibular glands of mice using a CRISPR/Cas9 genome editing system - Yi Gu; Hui Cao; Fei Li; Jianli Yu; Rui Nian; Dongxiao Feng; Jingtao Lin; Haipeng Song; Wenshuai Liu (World Journal of Microbiology and Biotechnology, 2020)

Comparison of chemical characteristics of PM2.5 during two winters in Xiangtan City in south central China - Xiao-Yao Ma; Zheng-Hui Xiao; Li-Zhi He; Yun-Jiang Cao; Ji-Song Liu (Journal of Atmospheric Chemistry, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Experiments on excitation and data processing of low-frequency vibroseis in permafrost area of the tibetan plateau - Yu-Kun Tian; Hai-xia Kang; Jie Cao; Juan Li; Hui Zhou; Yan-Yan Ma (Applied Geophysics, 2020)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

RNA-seq analysis reveals divergent adaptive response to hyper- and hypo-salinity in cobia, Rachycentron canadum - Danyu Cao; Jinfeng Li; Baosong Huang; Jiandong Zhang; Chuanhao Pan; Jiansheng Huang; Hui Zhou; Qian Ma; Gang Chen; Zhongliang Wang (Fish Physiology and Biochemistry, 2020)

The effects of a short-term exposure to propiconazole in zebrafish (Danio rerio) embryos - Feng Zhao; Fangjie Cao; Hui Li; Miaomiao Teng; Yong Liang; Lihong Qiu (Environmental Science and Pollution Research, 2020)

Molecular characterization of an emerging reassortant mammalian orthoreovirus in China - Dandan Ye; Zhaoyang Ji; Hongyan Shi; Jianfei Chen; Da Shi; Liyan Cao; Jianbo Liu; Mingwei Li; Hui Dong; Zhaoyang Jing; Xiaobo Wang; Qiuge Liu; et al. (Archives of Virology, 2020)

Characterization of Pneumocystis jirovecii pneumonia at three tertiary comprehensive hospitals in southern China - Yan-Hui Chen; Xue-Yao Fang; Yue-Ting Li; Yan-Ling Liu; Ya-Ping Hang; Yan-Ping Xiao; Xing-Wei Cao; Qiao-Shi Zhong; Long-Hua Hu (Brazilian Journal of Microbiology, 2020)

Development and validation of high-throughput and low-cost STARP assays for genes underpinning economically important traits in wheat - Yuying Wu; Ming Li; Zhonghu He; Susanne Dreisigacker; Weie Wen; Hui Jin; Shengnan Zhai; Faji Li; Fengmei Gao; Jindong Liu; Rongge Wang; Pingzhi Zhang; et al. (Theoretical and Applied Genetics, 2020)

Dynamic response and mechanical deformation properties of the soil cutting slope under train cyclic loads - Qiang Xie; Zhi-hui Wu; Chun-bo He; Jie Dong; Zhi-lin Cao; Li Liang (Arabian Journal of Geosciences, 2020)

HSV-1 infection and pathogenesis in the tree shrew eye following corneal inoculation - Lihong Li; Yan Li; Xin Li; Yujie Xia; Erlin Wang; Daohua Gong; Guijun Chen; Liping Yang; Ke Zhang; Zhuanghong Zhao; Nigel W. Fraser; Quanshui Fan; et al. (Journal of NeuroVirology, 2020)

NK cell reconstitution following unmanipulated HLA-mismatched/haploidentical transplantation compared with matched sibling transplantation - Li-Juan Hu; Xun-Hong Cao; Xing-Xing Yu; Xue-Fei Liu; Xiao-Su Zhao; Ying-Jun Chang; Xiao-Hui Zhang; Lan-Ping Xu; Yu Wang; Kai-Yan Liu; Xiao-Jun Huang; Xiang-Yu Zhao (Science China Life Sciences, 2020)

Multiple omics analysis of the protective effects of SFN on estrogen-dependent breast cancer cells - Hui Huang; Shuyuan Cao; Zhan Zhang; Lei Li; Feng Chen; Qian Wu (Molecular Biology Reports, 2020)

Synchrotron Radiation-Based Three-Dimensional Visualization of Angioarchitectural Remodeling in Hippocampus of Epileptic Rats - Pan Gu; Zi-Hao Xu; Yu-Ze Cao; Sheng-Hui Liao; Qian-Fang Deng; Xian-Zhen Yin; Zhuo-Lu Wang; Zhuo-Hui Chen; Xin-Hang Hu; Hui Wang; Li-Zhi Li; Shi-Xin Liu; et al. (Neuroscience Bulletin, 2020)

Correction to: AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

AVE0991, a nonpeptide angiotensin-(1–7) mimic, inhibits angiotensin II–induced abdominal aortic aneurysm formation in apolipoprotein E knockout mice - Hui Ma; Yu-Lin Wang; Nai-Hao Hei; Jun-Long Li; Xin-Ran Cao; Bo Dong; Wen-jiang Yan (Journal of Molecular Medicine, 2020)

FY-4A LMI Observed Lightning Activity in Super Typhoon Mangkhut (2018) in Comparison with WWLLN Data - Wenjuan Zhang; Wen Hui; Weitao Lyu; Dongjie Cao; Pengfei Li; Dong Zheng; Xiang Fang; Yijun Zhang (Journal of Meteorological Research, 2020)

Identifying common genome-wide risk genes for major psychiatric traits - Sha Liu; Shuquan Rao; Yong Xu; Jun Li; Hailiang Huang; Xu Zhang; Hui Fu; Qiang Wang; Hongbao Cao; Ancha Baranova; Chunhui Jin; Fuquan Zhang (Human Genetics, 2020)

Chronology of coastal aeolian deposition and its paleoenvironmental implications on the Liuao Peninsula of South China - Jian-hui Jin; Zhi-zhong Li; Zhi-yong Ling; Fei Zheng; Xiao-lin Xu; Yan Cheng; Xiang-dong Cao; Zhi-xing Li; Wen-jing Zhang; Yong-qing Ren (Journal of Mountain Science, 2019)

Ginsenoside compound K ameliorates Alzheimer’s disease in HT22 cells by adjusting energy metabolism - Xijun Chen; Hui Li; Qing Yang; Xingcheng Lan; Jifeng Wang; Zhanhong Cao; Xiaozheng Shi; Jing Li; Mo Kan; Xiaobo Qu; Na Li (Molecular Biology Reports, 2019)

Vanadium compounds induced damage of human umbilical vein endothelial cells and the protective effect of berberine - Cong-Cong Hou; Hong-Yu Liang; Yi-Hui Pan; Man Wang; Li-Li Zhao; Yuan Bian; Duan-Yuan Cao; Ding Zhao (BioMetals, 2019)

Nuclear localization signal in TRIM22 is essential for inhibition of type 2 porcine reproductive and respiratory syndrome virus replication in MARC-145 cells - Huiyuan Jing; Ran Tao; Nan Dong; Sufang Cao; Yanting Sun; Wenting Ke; Yang Li; Jinhe Wang; Yan Zhang; Hui Huang; Wang Dong (Virus Genes, 2019)

Dorsolateral striatal miR-134 modulates excessive methamphetamine intake in self-administering rats - Jing-Jing Shi; Dan-Ni Cao; Hui-Fen Liu; Zhi-Yuan Wang; Guan-Yi Lu; Ning Wu; Wen-Hua Zhou; Jin Li (Metabolic Brain Disease, 2019)

Reduced hemispheric asymmetry of brain anatomical networks in attention deficit hyperactivity disorder - Dandan Li; Ting Li; Yan Niu; Jie Xiang; Rui Cao; Bo Liu; Hui Zhang; Bin Wang (Brain Imaging and Behavior, 2019)

Geochronology, geochemistry and Sr-Nd-Pb-Hf isotopes of the Early Paleogene gabbro and granite from Central Lhasa, southern Tibet: petrogenesis and tectonic implications - Yun-hui Zhang; Hua-wen Cao; Steven P. Hollis; Li Tang; Mo Xu; Jun-sheng Jiang; Shun-bao Gao; Yang-shuang Wang (International Geology Review, 2019)

Inhibition of EPAC2 Attenuates Intracerebral Hemorrhage-Induced Secondary Brain Injury via the p38/BIM/Caspase-3 Pathway - Yan Zhuang; Hui Xu; Seidu A. Richard; Jie Cao; Haiying Li; Haitao Shen; Zhengquan Yu; Jian Zhang; Zhong Wang; Xiang Li; Gang Chen (Journal of Molecular Neuroscience, 2019)

Andrographolide impairs alpha-naphthylisothiocyanate-induced cholestatic liver injury in vivo - Lei Wang; Fei Cao; Li-li Zhu; Peng Liu; Yu-ru Shang; Wen-hui Liu; Xin Dong; Hai-dong Bao; Peng Gong; Zhong-yu Wang (Journal of Natural Medicines, 2019)

Geochemistry, zircon U–Pb geochronology and Hf isotopes of Jurassic-Cretaceous granites in the Tengchong terrane, SW China: implications for the Mesozoic tectono-magmatic evolution of the Eastern Tethyan Tectonic Domain - Hua-Wen Cao; Yun-Hui Zhang; Li Tang; Steven P. Hollis; Shou-Ting Zhang; Qiu-Ming Pei; Chang Yang; Xiao-Shuan Zhu (International Geology Review, 2019)

Loop-mediated isothermal amplification (LAMP) detection of Phytophthora hibernalis, P. syringae and P. cambivora - Guan-Rong Li; Guo-Ming Huang; Lin-Hui Zhu; Dajin Lv; Baohong Cao; Fang Liao; Jia-Feng Luo (Journal of Plant Pathology, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

A Genome-Wide Association Study of α-Synuclein Levels in Cerebrospinal Fluid - Xiao-ling Zhong; Jie-Qiong Li; Li Sun; Ya-Qing Li; Hui-Fu Wang; Xi-Peng Cao; Chen-Chen Tan; Ling Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Dual flow immunochromatographic assay for rapid and simultaneous quantitative detection of ochratoxin A and zearalenone in corn, wheat, and feed samples - Xian Zhang; Ke He; Yun Fang; Tong Cao; Narayan Paudyal; Xiao-feng Zhang; Hou-hui Song; Xiao-liang Li; Wei-huan Fang (Journal of Zhejiang University-SCIENCE B, 2018)

The relative importance of space compared to topography increases from rare to common tree species across latitude - Yue‐Hua Hu; Daniel J. Johnson; Xiang‐Cheng Mi; Xu‐Gao Wang; Wan‐Hui Ye; Yi‐De Li; Ju‐Yu Lian; Min Cao (Journal of Biogeography, 2018)
Aim Understanding how spatial distributions of rare and common species are associated with environmental and spatial processes is essential to understanding community assembly. We addressed the following questions: (a) does the relative importance of space and topography vary from rare to common tree species? (b) Are the contributions of topography and space equal? (c) Are the variances explained by topography or space correlated with elevational ranges (ER) at the local scale? (d) Does cell‐size influence those postulated associations? Location China and the Americas. Major taxa studied Tree species. Methods We partitioned the variation in species richness and composition of rare and common tree species by topography and space across a range of extents and grain sizes in eight communities. We calculated contribution ratio ( CR ) between space and topography to quantify their relative importance. We employed Kendall's rank correlation to determine the relation between CR and commonness. Mixed effect models were used to identify the influence of cell‐size on the results. Results The majority of CR values were positively related to increasing commonness, especially for composition. The explained variances by space were always higher than that by topography regardless of commonness. At local scale, variances explained by space or topography were not correlated with ER. Main conclusions Our results indicate that the relative importance of space compared to topography increases from rare to common species across forests. We suggest that future studies of community assembly need to account for both space and topography to adequately describe differences in rare and common species assembly mechanisms at range of spatial extents and grain sizes.

Anxiolytic potency of iridoid fraction extracted from Valeriana jatamansi Jones and its mechanism: a preliminary study - Xue-Mei Zhang; Jia-Li Zhu; Yong Sun; Yao-Lan Dai; Xiu Chen; Jia-Hong Cao; Ruo-Cong Yang; Chang Chen; Chao-Ying Ma; Tian-E Zhang; Yun-Hui Chen; Zhi-Yong Yan (Natural Product Research, 2018)

Genome-wide linkage mapping of yield-related traits in three Chinese bread wheat populations using high-density SNP markers - Faji Li; Weie Wen; Zhonghu He; Jindong Liu; Hui Jin; Shuanghe Cao; Hongwei Geng; Jun Yan; Pingzhi Zhang; Yingxiu Wan; Xianchun Xia (Theoretical and Applied Genetics, 2018)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Anemia and Iron Status Among Different Body Size Phenotypes in Chinese Adult Population: a Nation-Wide, Health and Nutrition Survey - Jiang Li; Cheng Xiao; Hui Yang; Yun Zhou; Rui Wang; Yongtong Cao (Biological Trace Element Research, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Risk factors, outcomes and genotypes of carbapenem-nonsusceptible Klebsiella pneumoniae bloodstream infection: a three-year retrospective study in a large tertiary hospital in Northern China - Si-Han Zheng; Sheng-Ji Cao; Hui Xu; Dan Feng; Li-Ping Wan; Guang-Jie Wang; Xiao-Guang Xiao (Infectious Diseases, 2018)

Triplex real-time PCR detection of three quarantine Phytophthora pathogens infecting Malus Miller - Fang Liao; Ying Zhang; Lin-Hui Zhu; Baohong Cao; Dajin Lv; Jia-Feng Luo; Guan-Rong Li (Journal of Plant Diseases and Protection, 2018)

Yield enhancement strategies of rare pharmaceutical metabolites from endophytes - Fangxue Xu; Shiyuan Wang; Yujuan Li; Mengmeng Zheng; Xiaozhi Xi; Hui Cao; Xiaowei Cui; Hong Guo; Chunchao Han (Biotechnology Letters, 2018)

Production of Humic Acid by a Bacillus megaterium Strain Using Vinasse - Nan Li; Zhi-Nian Deng; Yuan-Wen Wei; Hui-Qing Cao; Yang-Rui Li (Sugar Tech, 2018)

Quantitative proteomics of pomegranate varieties with contrasting seed hardness during seed development stages - Juan Niu; Da Cao; Haoxian Li; Hui Xue; Lina Chen; Beibei Liu; Shangyin Cao (Tree Genetics & Genomes, 2018)

Characteristics of polycyclic aromatic hydrocarbons in PM2.5 emitted from different cooking activities in China - Yun-Chun Li; Jia-Qian Qiu; Man Shu; Steven Sai Hang Ho; Jun-Ji Cao; Ge-Hui Wang; Xian-Xiang Wang; Xiao-Qing Zhao (Environmental Science and Pollution Research, 2018)

Climatology of cloud-base height from long-term radiosonde measurements in China - Yong Zhang; Lejian Zhang; Jianping Guo; Jinming Feng; Lijuan Cao; Yang Wang; Qing Zhou; Liangxu Li; Bai Li; Hui Xu; Lin Liu; Ning An; et al. (Advances in Atmospheric Sciences, 2018)

L1CAM drives oncogenicity in esophageal squamous cell carcinoma by stimulation of ezrin transcription - Jin-Cheng Guo; Yang-Min Xie; Li-Qiang Ran; Hui-Hui Cao; Chun Sun; Jian-Yi Wu; Zhi-Yong Wu; Lian-Di Liao; Wei-Jiang Zhao; Wang-Kai Fang; En-Min Li; Li-Yan Xu; et al. (Journal of Molecular Medicine, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Nortirucallane A, a new tirucallane-type nortriterpenoid isolated from Lonicerae japonicae flos - Xu Wang; Jing Zhang; Ya-qun Li; Bao-xiang Du; Qi-hui Sun; Yun-jiao Cao; Hai-qiang Jiang; Yu-hong Liu; Hong-lei Zhou; Rong Rong (Natural Product Research, 2017)

Evaluation on the Production of Food Crop Straw in China from 2006 to 2014 - Hui Li; Yan Cao; Xingming Wang; Xin Ge; Buqing Li; Chengqian Jin (BioEnergy Research, 2017)

Enhanced Degradation of Atrazine by Soil Microbial Fuel Cells and Analysis of Bacterial Community Structure - Hui Wang; Lei Li; Xian Cao; Xizi Long; Xianning Li (Water, Air, & Soil Pollution, 2017)

Overexpression of PLK3 Mediates the Degradation of Abnormal Prion Proteins Dependent on Chaperone-Mediated Autophagy - Hui Wang; Chan Tian; Jing Sun; Li-Na Chen; Yan Lv; Xiao-Dong Yang; Kang Xiao; Jing Wang; Cao Chen; Qi Shi; Qi-Xiang Shao; Xiao-Ping Dong (Molecular Neurobiology, 2017)

Developing the science product algorithm testbed for Chinese next-generation geostationary meteorological satellites: Fengyun-4 series - Min Min; Chunqiang Wu; Chuan Li; Hui Liu; Na Xu; Xiao Wu; Lin Chen; Fu Wang; Fenglin Sun; Danyu Qin; Xi Wang; Bo Li; et al. (Journal of Meteorological Research, 2017)

Prevalence of ammonia-oxidizing bacteria over ammonia-oxidizing archaea in sediments as related to nutrient loading in Chinese aquaculture ponds - Zijun Zhou; Hui Li; Chunlei Song; Xiuyun Cao; Yiyong Zhou (Journal of Soils and Sediments, 2017)

Puerarin may protect against Schwann cell damage induced by glucose fluctuation - Bing Xue; Lin Wang; Zhe Zhang; Rui Wang; Xin-xin Xia; Ping-ping Han; Li-jun Cao; Yong-hui Liu; Lian-qing Sun (Journal of Natural Medicines, 2017)

Distribution of phosphorus-solubilizing bacteria in relation to fractionation and sorption behaviors of phosphorus in sediment of the Three Gorges Reservoir - Yuqian Liu; Xiuyun Cao; Hui Li; Zijun Zhou; Siyang Wang; Zhicong Wang; Chunlei Song; Yiyong Zhou (Environmental Science and Pollution Research, 2017)

Optimized monitoring sites for detection of biodiversity trends in China - Haigen Xu; Mingchang Cao; Yi Wu; Lei Cai; Yun Cao; Hui Ding; Peng Cui; Jun Wu; Zhi Wang; Zhifang Le; Xiaoqiang Lu; Li Liu; et al. (Biodiversity and Conservation, 2017)

The effects of cadmium pulse dosing on physiological traits and growth of the submerged macrophyte Vallisneria spinulosa and phytoplankton biomass: a mesocosm study - Hui Liu; Yu Cao; Wei Li; Zhao Zhang; Erik Jeppesen; Wei Wang (Environmental Science and Pollution Research, 2017)

Transplantation of collagen scaffold with autologous bone marrow mononuclear cells promotes functional endometrium reconstruction via downregulating ΔNp63 expression in Asherman’s syndrome - Guangfeng Zhao; Yun Cao; Xianghong Zhu; Xiaoqiu Tang; Lijun Ding; Haixiang Sun; Juan Li; Xinan Li; Chenyan Dai; Tong Ru; Hui Zhu; Jingjie Lu; et al. (Science China Life Sciences, 2017)

U–Pb dating of zircon and cassiterite from the Early Cretaceous Jiaojiguan iron-tin polymetallic deposit, implications for magmatism and metallogeny of the Tengchong area, western Yunnan, China - Hua-Wen Cao; Yun-Hui Zhang; Qiu-Ming Pei; Rong-Qing Zhang; Li Tang; Bin Lin; Guo-Jun Cai (International Geology Review, 2017)

Aluminum Trichloride Inhibits the Rat Osteoblasts Mineralization In Vitro - Miao Song; Hui Huo; Zheng Cao; Yanfei Han; Li Gao (Biological Trace Element Research, 2017)

Olfactory Dysfunction in Parkinson’s Disease Patients with the LRRK2 G2385R Variant - Ming Cao; Zhu-Qin Gu; Yuan Li; Hui Zhang; Xiao-Juan Dan; Shan-Shan Cen; Da-Wei Li; Piu Chan (Neuroscience Bulletin, 2016)

Loop-mediated isothermal amplification assay targeting the mpb70 gene for rapid differential detection of Mycobacterium bovis - Hui Zhang; Zhen Wang; Xudong Cao; Zhengrong Wang; Jinliang Sheng; Yong Wang; Jing Zhang; Zhiqiang Li; Xinli Gu; Chuangfu Chen (Archives of Microbiology, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

Soil nitrate–N residue, loss and accumulation affected by soil surface management and precipitation in a winter wheat-summer fallow system on dryland - Gang He; Zhaohui Wang; Fucui Li; Jian Dai; Xiaolong Ma; Qiang Li; Cheng Xue; Hanbing Cao; Sen Wang; Hui Liu; Laichao Luo; Ming Huang; et al. (Nutrient Cycling in Agroecosystems, 2016)

Enhancement of sediment phosphorus release during a tunnel construction across an urban lake (Lake Donghu, China) - Siyang Wang; Hui Li; Jian Xiao; Yiyong Zhou; Chunlei Song; Yonghong Bi; Xiuyun Cao (Environmental Science and Pollution Research, 2016)

Molecular characterization and evolutionary origins of farinin genes in Brachypodium distachyon L. - Saminathan Subburaj; Nana Luo; Xiaobing Lu; Xiaohui Li; Hui Cao; Yingkao Hu; Jiarui Li; Yueming Yan (Journal of Applied Genetics, 2016)

Sediment–water interaction in phosphorus cycling as affected by trophic states in a Chinese shallow lake (Lake Donghu) - Xi Chen; Hui Li; Jie Hou; Xiuyun Cao; Chunlei Song; Yiyong Zhou (Hydrobiologia, 2016)

New process for copper migration by bioelectricity generation in soil microbial fuel cells - Hui Wang; Hailiang Song; Ran Yu; Xian Cao; Zhou Fang; Xianning Li (Environmental Science and Pollution Research, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Dietary Selenium Status Regulates the Transcriptions of Selenoproteome and Activities of Selenoenzymes in Chicken Kidney at Low or Super-nutritional Levels - Jing-Xiu Xu; Cong Zhang; Chang-Yu Cao; Shi-Yong Zhu; Hui Li; Yan-Chun Sun; Jin-Long Li (Biological Trace Element Research, 2016)

Simulation of the interface between the Indian summer monsoon and the East Asian summer monsoon: Intercomparison between MPI-ESM and ECHAM5/MPI-OM - Yiran Guo; Jie Cao; Hui Li; Jian Wang; Yuchao Ding (Advances in Atmospheric Sciences, 2016)

Low-Dose Topical 5-Aminolevulinic Acid Photodynamic Therapy in the Treatment of Different Severity of Acne Vulgaris - Shi-qin Tao; Fei Li; Lei Cao; Ru-shan Xia; Hua Fan; Ying Fan; Hui Sun; Cheng Jing; Li-jia Yang (Cell Biochemistry and Biophysics, 2015)

Effect of allelopathy on the competition and succession of Skeletonema costatum and Prorocentrum donghaiense - Yiwen Zhang; Jiangtao Wang; Liju Tan; Jing Cao; Hui Li (Marine Biology Research, 2015)

Effects of Cu2+ and Zn2+ on growth and physiological characteristics of green algae, Cladophora - De-ju Cao; Pan-pan Xie; Juan-wei Deng; Hui-min Zhang; Ru-xiao Ma; Cheng Liu; Ren-jing Liu; Yue-gan Liang; Hao Li; Xiao-dong Shi (Environmental Science and Pollution Research, 2015)

Differential expression and regulation of Runx1 in mouse uterus during the peri-implantation period - Zhi-Kun Bai; Dang-Dang Li; Chuan-Hui Guo; Zhan-Qing Yang; Hang Cao; Bin Guo; Zhan-Peng Yue (Cell and Tissue Research, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Replacement of fish meal by meat and bone meal in diets for juvenile snakehead Ophiocephalus argus - Hairui Yu; Qin Zhang; Hui Cao; Tong Tong; Guoqiang Huang; Weizhong Li (Fisheries Science, 2015)

Serum Aβ is Predictive for Short-Term Neurological Deficits After Acute Ischemic Stroke - Yu-Hui Liu; Hong-Yuan Cao; Ye-Ran Wang; Shu-Sheng Jiao; Xian-Le Bu; Fan Zeng; Qing-Hua Wang; Jing Li; Juan Deng; Hua-Dong Zhou; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Scrapie Infection in Experimental Rodents and SMB-S15 Cells Decreased the Brain Endogenous Levels and Activities of Sirt1 - Jing Wang; Jin Zhang; Qi Shi; Bao-Yun Zhang; Cao Chen; Li-Na Chen; Jing Sun; Hui Wang; Kang Xiao; Xiao-Ping Dong (Journal of Molecular Neuroscience, 2015)

Levels and environmental impact of PAHs and trace element in fly ash from a miscellaneous solid waste by rotary kiln incinerator, China - Hui Li; Guijian Liu; Yan Cao (Natural Hazards, 2015)

Differential expression and regulation of Ido2 in the mouse uterus during peri-implantation period - Dang-Dang Li; Xin-Yuan Liu; Chuan-Hui Guo; Liang Yue; Zhan-Qing Yang; Hang Cao; Bin Guo; Zhan-Peng Yue (In Vitro Cellular & Developmental Biology - Animal, 2015)

Erythropoietin (EPO) Protects Against High Glucose-Induced Apoptosis in Retinal Ganglional Cells - Yunxiao Wang; Hui Zhang; Yanping Liu; Ping Li; Zhihong Cao; Yu Cao (Cell Biochemistry and Biophysics, 2015)

Ischemic Preconditioning Provides Neuroprotection by Induction of AMP-Activated Protein Kinase-Dependent Autophagy in a Rat Model of Ischemic Stroke - Teng Jiang; Jin-Tai Yu; Xi-Chen Zhu; Qiao-Quan Zhang; Meng-Shan Tan; Lei Cao; Hui-Fu Wang; Jian-Quan Shi; Li Gao; Hao Qin; Ying-Dong Zhang; Lan Tan (Molecular Neurobiology, 2015)

Isolation and characterization of dengue virus serotype 2 from the large dengue outbreak in Guangdong, China in 2014 - Hui Zhao; LingZhai Zhao; Tao Jiang; XiaoFeng Li; Hang Fan; WenXin Hong; Yu Zhang; Qin Zhu; Qing Ye; YiGang Tong; WuChun Cao; FuChun Zhang; et al. (Science China Life Sciences, 2014)

Isoflurane Protects Against Injury Caused by Deprivation of Oxygen and Glucose in Microglia Through Regulation of the Toll-Like Receptor 4 Pathway - Hai-Fei Xiang; Dong-Hang Cao; Yan-Qing Yang; Hui-Qin Wang; Li-Jun Zhu; Bin-Hao Ruan; Jing Du; Ming-Cang Wang (Journal of Molecular Neuroscience, 2014)

Bernoulli-based random undersampling schemes for 2D seismic data regularization - Rui Cai; Qun Zhao; De-Ping She; Li Yang; Hui Cao; Qin-Yong Yang (Applied Geophysics, 2014)

New species and new records of Rhytismataceae from Japan - Zhi-Jie Li; Ning Cao; Hui-Fen Chen; J. E. Taylor; Cheng-Lin Hou (Mycological Progress, 2014)

Cascade effects of crop species richness on the diversity of pest insects and their natural enemies - PeiJian Shi; Cang Hui; XingYuan Men; ZiHua Zhao; Fang Ouyang; Feng Ge; XianShi Jin; HaiFeng Cao; B. Larry Li (Science China Life Sciences, 2014)

Evolution of High-Affinity Peptide Probes to Detect the SH3 Domain of Cancer Biomarker BCR–ABL - Hui-Min Liu; Li-Juan Li; Juan Guo; Zhan-Jia Yang; Xiao Yang; Run-Peng Qi; Wei Cao (International Journal of Peptide Research and Therapeutics, 2014)

Preliminary study on the utilization of Ca2+ and HCO3 − in karst water by different sources of Chlorella vulgaris - Pei Wang; Qingjing Hu; Hui Yang; Jianhua Cao; Liang Li; Yi Liang; Kairan Wang (Carbonates and Evaporites, 2014)

Analysis of quality factors for Rayleigh channel waves - Xiao-Hui Yang; Si-Yuan Cao; De-Chun Li; Peng-Fei Yu; Hao-Ran Zhang (Applied Geophysics, 2014)

The PpLTP1 Primary Allergen Gene is Highly Conserved in Peach and Has Small Variations in Other Prunus Species - Ying-tao Ma; Xiang Zhou; Zhong-shan Gao; Xiong-wei Li; Hui-juan Jia; Hong-xia Wu; Rang-jin Xie; Zhi-qiang Wang; Ming-liang Yu; Ke Cao; Shuang-jian Chen; Ying-hui Li; et al. (Plant Molecular Biology Reporter, 2013)

Comparative Analysis of Gene Expression Profiles Between Cortex and Thalamus in Chinese Fatal Familial Insomnia Patients - Chan Tian; Di Liu; Qing-Lan Sun; Chen Chen; Yin Xu; Hui Wang; Wei Xiang; Hans A Kretzschmar; Wei Li; Cao Chen; Qi Shi; Chen Gao; et al. (Molecular Neurobiology, 2013)

pORF5 plasmid protein of Chlamydia trachomatis induces MAPK-mediated pro-inflammatory cytokines via TLR2 activation in THP-1 cells - Hui Zhou; QiuLin Huang; ZhongYu Li; YiMou Wu; XiaoBing Xie; KangKang Ma; WenJuan Cao; Zhou Zhou; ChunXue Lu; GuangMing Zhong (Science China Life Sciences, 2013)

RETRACTED ARTICLE: Mesothelial cells differentiate into fibroblast-like cells under the scirrhous gastric cancer microenvironment and promote peritoneal carcinomatosis in vitro and in vivo - Zhi-Dong Lv; Hai-Bo Wang; Qian Dong; Bin Kong; Jian-guo Li; Zhao-Chuan Yang; Hui-Li Qu; Wei-Hong Cao; Hui-Mian Xu (Molecular and Cellular Biochemistry, 2013)

AppA C-terminal Plays an Important Role in its Thermostability in Escherichia coli - Baojin Fei; Yu Cao; Hui Xu; Xinran Li; Tao Song; Zhongan Fei; Dairong Qiao; Yi Cao (Current Microbiology, 2013)

Phylogenetic diversity of bacterial endophytes of Panax notoginseng with antagonistic characteristics towards pathogens of root-rot disease complex - Li Ma; Yong Hong Cao; Ming Hui Cheng; Ying Huang; Ming He Mo; Yong Wang; Jian Zhong Yang; Fa Xiang Yang (Antonie van Leeuwenhoek, 2013)

Resveratrol prevents hepatic steatosis induced by hepatitis C virus core protein - Lina Jiang; Yu Gu; Jing Ye; Fang Liu; Yilin Zhao; Chao Wang; Yuqiao Xu; Xiangmei Cao; Liying Zhang; Wenpeng Dong; Fanfan Li; Jing Wang; et al. (Biotechnology Letters, 2012)

Comparative analysis of essential oil components of Evodia rutaecarpa (Juss.) Benth. var. officinalis (Dode) Huang and Evodia rutaecarpa (Juss.) Benth. - Guang-Xian Cai; Dan Huang; Shun-Xiang Li; Fei Xu; Lu Wang; Yan-Hui Lu; Liang Cao; Bao-Yang Wei; Ya Li; Ping Cai (Natural Product Research, 2012)

A dose-dependent function of follicular fluid on the proliferation and differentiation of umbilical cord mesenchymal stem cells (MSCs) of goat - Pubin Qiu; Yaofu Bai; Chao Liu; Xin He; Hui Cao; Mingzhao Li; Haijing Zhu; Jinlian Hua (Histochemistry and Cell Biology, 2012)

Reaction temperature alters chorzoxazone metabolism in carp (Cyprinus carpio) hepatic microsomes - Zaijian Li; Weiyuan Zhang; Xiaocong Lu; Jing Li; Bin He; Hui Jiang; Shasha Wang; Zheng Lu; Chunmei Wang; Jiyue Cao (Fish Physiology and Biochemistry, 2012)

Clinical significance of peritumoral lymphatic vessel density and lymphatic vessel invasion detected by D2-40 immunostaining in FIGO Ib1-IIa squamous cell cervical cancer - Ying Xiong; Li-Ping Cao; Hui-Lan Rao; Mu-Yan Cai; Li-Zhi Liang; Ji-Hong Liu (Cell and Tissue Research, 2012)

Molecular cloning and functional characterization of a novel apple MdCIPK6L gene reveals its involvement in multiple abiotic stress tolerance in transgenic plants - Rong-Kai Wang; Ling-Li Li; Zhong-Hui Cao; Qiang Zhao; Ming Li; Ling-Yun Zhang; Yu-Jin Hao (Plant Molecular Biology, 2012)

Divalent Metal Transporter 1 Expression and Regulation in Human Placenta - Yan-Qin Li; Bin Bai; Xiao-Xiao Cao; Yao-Hui Zhang; Hong Yan; Quan-Qing Zheng; Gui-Hua Zhuang (Biological Trace Element Research, 2012)

Polymorphisms in chicken extracellular fatty acid binding protein gene - Zhi-yuan Zhao; Li Zhang; Bing-wang Du; Ning-xian Cao; Xin-sheng Jiang; Wen-xia Tian; Shu-jun Li; Wei-wei Wu; Chang-hui Ye (Molecular Biology Reports, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Identification and characterization of a new naringinase-producing strain, Williopsis californica Jmudeb007 - Hui Ni; Lijun Li; Anfeng Xiao; Ying Cao; Yuelong Chen; Huinong Cai (World Journal of Microbiology and Biotechnology, 2011)

Using COI gene sequence to barcode two morphologically alike species: the cotton bollworm and the oriental tobacco budworm (Lepidoptera: Noctuidae) - Qing-Qing Li; Di-Yan Li; Hui Ye; Xiao-Fei Liu; Wei Shi; Neng Cao; Yan-Qing Duan (Molecular Biology Reports, 2011)

Mangrove trees affect the community structure and distribution of anammox bacteria at an anthropogenic-polluted mangrove in the Pearl River Delta reflected by 16S rRNA and hydrazine oxidoreductase (HZO) encoding gene analyses - Meng Li; Yi-Guo Hong; Hui-Luo Cao; Ji-Dong Gu (Ecotoxicology, 2011)

Increased JNK1 activity contributes to the upregulation of ApoD in the apocrine secretory gland cells from axillary osmidrosis - Hui Chen; Yingli Li; Jie Du; Yan Cao; Xiaoli Li (Molecular and Cellular Biochemistry, 2011)

Site-Directed Mutagenesis and Thermostability of Xylanase XYNB from Aspergillus niger 400264 - Jie Xie; Lingling Song; XinRan Li; XiuLi Yi; Hui Xu; Jing Li; Dairong Qiao; Yi Cao (Current Microbiology, 2011)

A mild and efficient synthesis of monofluorinated α-lactam pseudopeptides via a novel dehydrofluorination of Ugi products - Nianjin Liu; Song Cao; Jingjing Wu; Li Shen; Jinlong Yu; Jian Zhang; Hui Li; Xuhong Qian (Molecular Diversity, 2010)

Incidence and risk of significantly raised blood pressure in cancer patients treated with bevacizumab: an updated meta-analysis - Mao Mao An; Zui Zou; Hui Shen; Ping Liu; Meng Li Chen; Yong Bing Cao; Yuan Ying Jiang (European Journal of Clinical Pharmacology, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Neural circuits and temporal plasticity in hindlimb representation of rat primary somatosensory cortex: revisited by multi-electrode array on brain slices - Dan-Dan Wang; Zhen Li; Ying Chang; Rui-Rui Wang; Xue-Feng Chen; Zhen-Yu Zhao; Fa-Le Cao; Jian-Hui Jin; Ming-Gang Liu; Jun Chen (Neuroscience Bulletin, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Improvement of heart function in postinfarct heart failure swine models after hepatocyte growth factor gene transfer: comparison of low-, medium- and high-dose groups - Zhi-jian Yang; Bo Chen; Zhang Sheng; Ding-guo Zhang; En-zhi Jia; Wei Wang; Dong-chao Ma; Tie-bing Zhu; Lian-sheng Wang; Chun-jian Li; Hui Wang; Ke-jiang Cao; et al. (Molecular Biology Reports, 2010)

The polymorphisms of UCP1 genes associated with fat metabolism, obesity and diabetes - Jun-jing Jia; Yun-bo Tian; Zhen-hui Cao; Lin-li Tao; Xi Zhang; Si-zhen Gao; Chang-rong Ge; Qiu-Ye Lin; M. Jois (Molecular Biology Reports, 2010)

Sex ratio deviation of offspring in the area where exposure to the processing of electronic wastes - Qiang Liu; Ke Qiu Li; Jia Cao; Hui Zhao; Guang Li; Fei Yue Fan (Environmental Science and Pollution Research, 2010)

Isolation and characterization of microsatellite markers for Cycas hainanensis C. J. Chen (Cycadaceae) - Min Zhang; Zheng-Feng Wang; Shu-Guang Jian; Wan-Hui Ye; Hong-Lin Cao; Peng Zhu; Ling Li (Conservation Genetics, 2009)

Isolation and characterization of ten polymorphic microsatellite in the endangered tree Erythrophleum fordii oliv - Peng Zhu; Wan-Hui Ye; Zheng-Feng Wang; Hong-Lin Cao; Min Zhang; Ling Li; Wei Xiao (Conservation Genetics, 2009)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

Molecular mutations associated with the in vitro passage of virulent porcine reproductive and respiratory syndrome virus - Wei Han; Jia-Jun Wu; Xiao-Yu Deng; Zhen Cao; Xiu-ling Yu; Chuan-Bin Wang; Tie-Zhu Zhao; Nan-Hua Chen; Hong-Hui Hu; Wang Bin; Li-Li Hou; Li-Lin Wang; et al. (Virus Genes, 2009)

Association of the mutation for the human carboxypeptidase E gene exon 4 with the severity of coronary artery atherosclerosis - En-Zhi Jia; Jie Wang; Zhi-Jian Yang; Tie-Bing Zhu; Lian-Sheng Wang; Hui Wang; Chun-Jian Li; BO Chen; Ke-Jiang Cao; Jun Huang; Wen-Zhu Ma (Molecular Biology Reports, 2009)

Identification of QTLs for the resistance to rice stripe virus in the indica rice variety Dular - Shu-Jun Wu; Huan Zhong; Yong Zhou; Hui Zuo; Li-Hui Zhou; Jin-Yan Zhu; Cao-Qiu Ji; Shi-Liang Gu; Ming-Hong Gu; Guo-Hua Liang (Euphytica, 2009)

Liver-specific ZP domain-containing protein (LZP) as a new partner of Tamm-Horsfall protein harbors on renal tubules - Hai-Lian Shen; Zhi-Gang Xu; Li-Yu Huang; Dong Liu; Dao-Hong Lin; Jia-Bin Cao; Xin Zhang; Zhi-Qin Wang; Wen-Hui Wang; Peng-Yuan Yang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2009)

Identification and characterization of EST-SSRs and cpSSRs in endangered Cycas hainanensis - Zheng-Feng Wang; Wan-Hui Ye; Hong-Lin Cao; Zhong-Chao Li; Shao-Lin Peng (Conservation Genetics, 2008)

Fibronectin-mediated activation of Akt2 protects human ovarian and breast cancer cells from docetaxel-induced apoptosis via inhibition of the p38 pathway - Hui Xing; Yang Cao; Danhui Weng; Wenming Tao; Xiaohong Song; Wei Wang; Li Meng; Gang Xu; Jianfeng Zhou; Shixuan Wang; Ding Ma (Apoptosis, 2008)

A simple and effective method for protein subcellular localization using Agrobacterium-mediated transformation of onion epidermal cells - Wei Sun; Ziyi Cao; Yan Li; Yanxiu Zhao; Hui Zhang (Biologia, 2007)

Site-Directed Mutagenesis of Aeromonas hydrophila Enoyl Coenzyme A Hydratase Enhancing 3-Hydroxyhexanoate Fractions of Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) - Fengqing Hu; Yan Cao; Fang Xiao; Jin Zhang; Hui Li (Current Microbiology, 2007)

NYD-SP15: A Novel Gene Potentially Involved in Regulating Testicular Development and Spermatogenesis - Qinghuai Liu; Jin Liu; Qinhong Cao; Jiahao Sha; Zuomin Zhou; Hui Wang; Jianmin Li (Biochemical Genetics, 2006)

Cloning and expression study of a putative high-affinity nitrate transporter gene from Dunaliella salina - Qinghua He; Dairong Qiao; Qinglian Zhang; Yin Li; Hui Xu; Liang Wei; Ying Gu; Yi Cao (Journal of Applied Phycology, 2004)